GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 717651109 species occurrences available in GBIF matching the query: HasCoordinate: true TaxonKey: Animalia HasGeospatialIssue: false. The dataset includes 717651109 records from 11629 constituent datasets: 8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 3 records from The taxonomic status of Long-tailed shrews (Mammalia: genus Sorex) from Nuclear Central America. 3 records from Another alien on the horizon? First European record of Tautoneura polymitusa, an East Asian leafhopper (Hemiptera: Auchenorryncha: Cicadellidae). 21 records from (Table 2) Distribution chart of calcareous nannofossils of ODP Hole 135-834A. 2260 records from cariaco-phytoplankton. 422 records from Brood cell No. of trap-nesting species Schorfheide 2008. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 4 records from A new genus Austrimonus for Eutettix melaleucae Kirkaldy (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini) and nine new species. 18 records from Taxonomic review of the genus Pygophora Schiner of Japan (Diptera: Muscidae). 2 records from Synaptus iranicus sp. nov., a second species of the genus Synaptus Eschscholtz, 1829 from Iran (Coleoptera: Elateridae) discovered by an integrative approach. 760 records from Global subterranean fishes. 398 records from Cephalaspidean Gastropods. 25 records from Foraminifera abundance of Hole 57-438. 102 records from Schulgelände Dientzenhofer-Gymnasium (Bamberg). 86 records from Renaturierung Werse (Innenbereich Beckum). 44 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 170 records from Density estimates of spotted handfish (Brachionichthys hirsutus) - GPS Underwater Visual Census (2015,2016). 599 records from CNAN/Arañas sinantrópicas. 57117 records from Mammals Specimens. 2 records from Two new species of Leptogenys from southern Brazil (Hymenoptera: Formicidae). 526 records from Ants: Formica Exsecta Records (Scotland). 2 records from Pollen record of profile 2TZ2. 22 records from (Table 2) Distribution of calcareous nannofossils in the Paleocene of ODP Hole 113-689B. 794 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE258. 60 records from The Peacock Spiders (Araneae: Salticidae: Maratus) of the Queensland Museum, including six new species. 64 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 9 records from (Table 1) Distribution of plaktonic foraminifers in ODP Hole 125-786A. 70 records from (Appendix) Late Cretaceous calcareous nannofossils of DSDP Holes 80-549 and 80-551. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 150 records from Ostracoda abundance of Hole 42-372. 211 records from Nannofossil abundance of Hole 64-476. 6526 records from FBIP: Systematics of South African Hymenoptera. 263 records from Butterberg, Dardesheim. 2 records from Abundance of radiolaria at station UT99-19-2. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 124 records from Anfibios y reptiles de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 5017 records from Actualización de la taxonomía y distribución de los anfibios y reptiles de San Luis Potosí. 142 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 6 records from Three new species of Pambolus (Braconidae: Pambolinae) from Mexico, with comments on the variation of P. oblongispina Papp. 8 records from Ohemoor (Hamburg/Norderstedt). 29 records from Ichthyological Collection of the Museu Oceanográfico D. Carlos I. 782 records from Otters: Northern Ireland Otter Survey Database. 2 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 6 records from Synonymy of Reikosiella Yoshimoto under Merostenus Walker (Hymenoptera: Chalcidoidea: Eupelmidae), with a checklist of world species and a revision of those species with brachypterous females. 1 records from Tallinn Botanic Garden. 808 records from Bee species and numbers caught by coloured pan traps across 20 landscapes in 2012, The Netherlands. 175970 records from Florida Keys Reef Visual Census 1997. 228 records from Données 2014 de l'Observatoire de la Biodiversité des Forêts. 22444 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 5 records from A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Magdalena River, Tolima, Colombia. 2 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 160 records from New and little known bees of the genus Sphecodes Latreille, 1804 (Hymenoptera: Apoidea: Halictidae) from Central Asia. 39923 records from Collection of saproxylic and xylobiont Beetles. 76 records from SNH Invertebrate Site Condition Monitoring 2015-16: Crannach Wood SSSI. 6801 records from MBML-Repteis - Coleção de Répteis. 37 records from Données naturalistes de Romain SORDELLO. 3523 records from INNS records held by BIS in Powys and Brecon Beacons National Park. 50 records from (Table 1) Time series of ostracod population density off Bokniseck shore ('Hausgarten'), western Baltic Sea. 16931 records from Poissons d'eau douce de Guyane française. 4 records from A second species of the genus Martensolasma (Opiliones, Dyspnoi, Nemastomatidae) from Mexico. 11059 records from Inventario de corales pétreos, anélidos, crustáceos decápodos, moluscos, equinodermos y peces óseos de los arrecifes coralinos de Guerrero y Oaxaca. 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 208 records from (Table 6) Planktonic foraminifer abundance of ODP Hole 162-982B. 1 records from Planktic foraminifera abundance of Hole 29-278. 7 records from Planktic foraminifera abundance of Hole 17-165. 24 records from Occurrence of mammalia relicts at site Trafalgar Square. 69 records from Occurrence of mammalia relicts at site l´Abri Caminade-Est. 5970 records from North East Scotland Amphibians & Reptiles 1850 - 2016. 2714 records from GEO Hauptveranstaltung Tirol (Innsbruck). 260 records from Inventaire malacologique du site Natura 2000 FR9301545 Venterol - Piegut - Grand Vallon (2006, ONF/MNHN). 110 records from Plotmatrix 2008 Alb Hainich Schorfheide Durchgang1. 525 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 8 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV8. 5 records from Pollen record of profile 3TZ2. 84 records from Pollen profile Bruchberg 1, Harz, Germany. 5 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 807 records from Water mite collection of Pauli Bagge. 19 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 6 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-8. 4 records from Reptilien und Insekten Entdecker / Schulgelände BBS Rotenburg. 2 records from ZUEC-DIP - Coleção de Diptera do Museu de Zoologia da UNICAMP. 6720 records from Registros ictiofaunísticos de localidades selectas de 10 regiones marinas prioritarias del Pacífico Mexicano. 46 records from Ostracoda abundance of Hole 34-320B. 20 records from A new species of Polyplocia Lestage from Malaysia with comments on the genus (Ephemeroptera, Euthyplociidae, Euthyplociinae). 10 records from New records of cotylean flatworms (Platyhelminthes: Polycladida: Rhabditophora) from coastal habitats of Israel. 114 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 1445 records from Bedfordshire Orthoptera (BNHS) - 1975-1990. 533 records from The near-bottom plankton and benthic invertebrate fauna of Josephine and Great Meteor Seamounts (Table 2). 152 records from Scratching the surface? Taxonomic revision of the subgenus Schizoptera (Odontorhagus) reveals vast undocumented biodiversity in the largest litter bug genus Schizoptera Fieber (Hemiptera: Dipsocoromorpha). 95338 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. 2852 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 132 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 36 records from Kaisertal. 78 records from Wasserwerkspark (Chemnitz). 12 records from Kindergarten. 2 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 19264 records from CSIRO, fish surveys by the Soela, 1980s. 2 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 2058 records from Données naturalistes de Julien BRISSET. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 9879 records from Bibliographic records of Angola mammals. 3 records from On Jungicephus Maa (Hymenoptera: Cephidae) with description of a new species from China. 221 records from Loup 2012 présence régulière communale (réseau Loup-Lynx ONCFS). 9945 records from ZFMK Orthopteroidea collection. 19 records from A taxonomic monograph of the leaf-litter inhabiting weevil genus Plumolepilius new genus (Coleoptera: Curculionidae: Molytinae: Conotrachelini) from Mexico, Guatemala, and El Salvador. 2 records from The types of Phasmida in the Natural History Museum, London, UK. 3509 records from Entocytheridae (Ostracoda) World Database. 6 records from The spiny theridiid genus Meotipa Simon, 1895 in India, with description of a strange new species with translucent abdomen and a phylogenetic analysis about the genus placement (Araneae, Theridiidae). 1102 records from Situación actual de ocho especies de anfibios en categoría de riesgo en Veracruz. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1985 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2 records from Two new species of brackish-water Macrostomum (Platyhelminthes, Macrostomida) from southern China. 19 records from Mayflies of the genus Epeorus Eaton, 1881 s. l. (Ephemeroptera: Heptageniidae) from the Caucasus Mountains: a new species of Caucasiron Kluge, 1997 from Georgia and Turkey. 1 records from Acrosternum heegeri Fieber, 1861 (Hemiptera: Heteroptera: Pentatomidae), another Mediterranean bug expanding to the north. 1801 records from Alterra (NL) - Entomofauna inventory in dead wood. 12 records from Auchenorrhyncha types (Hemiptera) deposited in Hayk Mirzayans Insect Museum. 21 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 21716 records from Cowan Tetrapod Collection - Birds. 50 records from tick monitoring Alb 2008 to 2010. 114 records from Chough sightings data, Northern Ireland, 2007-2010. 176 records from Données naturalistes du Comité départemental de l'Essonne (CODEP91) de la Fédération Française d'Etudes et de Sports Sous-Marins. 338660 records from Dénombrements d'oiseaux d'eau/Wetlands. 46 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 1 records from Eucharitidae new to the fauna of Saudi Arabia (Hymenoptera: Chalcidoidea), with the description of a new species and the previously unknown male of Eucharis (Psilogastrellus) albipennis Bouček. 1239 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 64 records from Evaluación bioecológica y ambiental de las áreas arrecifales del Caribe colombiano. 1422 records from Colección Hidrobiológica del Chocó. 264 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 60509 records from QLD DERM Coastal Bird Atlas (Trial). 41 records from Marine Sightings & Miscellaneous species records from Natural Resources Wales (NRW), 2008 onwards. 24 records from Comunidad de Herpetos Presentes en la Ciénaga de Montaño, Municipio del Carmen de Atrato. 52222 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 3282 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 18 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 28 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 7443 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 8245 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 378 records from Colección de Entomología - Hymenoptera - Aculeata. 1344 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 1 records from Morphological and molecular evidence for a new species of freshwater crab of the genus Sudanonautes Bott, 1955 (Brachyura: Potamoidea: Potamonautidae) from Cameroon, with notes on its ecology. 25794 records from TESRI-FB-EnjoyMoths. 9 records from The Pinnotheridae of the northeastern Pacific (Alaska to Mexico): zoogeographical remarks and new bivalve hosts (Crustacea, Brachyura, Pinnotheridae). 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 4 records from Collection Mammalia SMF. 15 records from Revision of Diplosynapsis Enderlein, 1914 (Diptera, Asilidae, Asilinae) with description of four new species. 15 records from Occurrence of mammalia relicts at site Grotte de la Martine. 44 records from Occurrence of mammalia relicts at site Pavlov. 198 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 2491 records from Collections data on ecology of bottom animal of the Southern ocean. 40080 records from Données naturalistes de CERCOPE (Jean-Louis PRATZ). 11235 records from ACT Wildlife Atlas. 1131 records from Rare marine fishes taken in Irish waters from 1786 to 2008. 40 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 304 records from Agriculture and Agri-Food Canada, Saskatoon. 12 records from Systematics of the Satyrium (Superflua) deria (Moore, 1865) species group with description of a new species from Afghanistan (Lepidoptera, Lycaenidae). 6106 records from SPC CoFish Invertebrates Observations Federated States of Micronesia 2006. 3 records from Pollen record of profile 3TZ1. 32 records from (Table 1) Distribution of calcareous nannofossils in the Eocene of ODP Hole 113-689B. 3160 records from Museo Nacional de Ciencias Naturales. CSIC, Madrid: MNCN-Nemata. 34 records from (Figure 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-641A. 6 records from (Table 4) Numerical abundances of nannofossil taxa in ODP Hole 126-792A. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 76 records from Lesser Spotted Woodpecker sample survey in England 2007. 2194 records from CSIRO, Jack Mackerel surveys, 1978. 259 records from Nannofossil abundance of Hole 73-522. 6 records from Phytoplankton abundance at stations off Paita in August 1995, Piura, Peru. 15 records from Inventaire participatif des rhopalocères de Bois-Guillaume, Bihorel et Isneauville. 14 records from Naturhausgarten. 200 records from Birdrace-Meister_der_Herzen-Kleve. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 1 records from Rediscovery of the Endangered frog Phrynopus montium (Shreve, 1938) (Amphibia, Anura, Craugastoridae) in the cloud forest of central Peru. 2 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 10138 records from Données ONEMA BDMAP 2013. 2 records from Macrobiotus nebrodensis and Adropion vexatum, two new species of Eutardigrada (Tardigrada, Parachela) from Sicily. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 78 records from The Mysidae (Crustacea: Peracarida: Mysida) in fresh and oligohaline waters of the Mediterranean. Taxonomy, biogeography, and bioinvasion. 1 records from A description of Macrobiotus horningi sp. nov. and redescriptions of M. maculatus comb. nov. Iharos, 1973 and M. rawsoni Horning et al., 1978 (Tardigrada: Eutardigrada: Macrobiotidae: hufelandi group). 12068 records from Beetles (LSM). 78 records from NE Scotland fungus and lichen records 1800-2010. 7497 records from Leicestershire and Rutland Reptile Records to 2011. 5306 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 16566 records from Invasive species - American bullfrog (Lithobates catesbeianus) in Flanders, Belgium. 1098 records from Poissons et Crustacés d'eau douce de Polynésie Française. 2584 records from Registros Primates Neotropicales Convocatoria APC. 1 records from Synthèse de la Répartition des populations de cerf sika en 2013 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2373 records from Waarneming.nl (NL) - Great Grey Shrike Count 2008-2009. 871 records from Isotope tracer experiment: nematode abundance. 5879 records from Inventario de los mamíferos pequeños y medianos de las zonas áridas y semiáridas de Baja California. 14 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 21 records from Bird specimens of Toyota City Nature Sanctuary. 1713 records from Données Circus maillardi du Parc national de La Réunion - COBE02. 9893 records from Colección de Tejidos del Instituto Alexander Von Humboldt. 3 records from Range table from planktonic foraminifers in ODP Hole 152-916A. 8 records from Planktic foraminifera abundance of Hole 94-611C. 74932 records from KUBI Ichthyology Collection. 48 records from Occurrence of mammalia relicts at site Groß-Rohrheim. 444 records from Occurrence of mammalia relicts at site Kalman Lambrecht Cave. 439 records from Occurrence of mammalia relicts at site Veternica. 78 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 4 records from A new species of Yllenus Simon, 1868 from northern India (Araneae, Salticidae). 4574 records from Revue Alexanor [1959-]. 1112 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 357 records from Actinopterygius Specimens of Akita Prefectural Museum. 90 records from Crustacea specimens of Kuroshio Biological Research Foundation. 6 records from New data of three rare belondirid species (Nematoda, Dorylaimida, Belondiridae) from Vietnam, with the first record and description of the male of Oxybelondira paraperplexa Ahmad & Jairajpuri, 1979. 1 records from Pollen record of profile L11. 67302 records from ummz_mollusks. 83 records from (Table 3) Benthic foraminiferal assemblage in the late Pliocene interval of Site 162-984. 26 records from (Table 19) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-593. 23913 records from Seasearch Marine Surveys in the Isle of Man. 3 records from A distinct new species of riparian rock-dwelling gecko (genus: Hemidactylus) from the southern Western Ghats. 450 records from SNH Invertebrate Site Condition Monitoring 2015-16: Den of Airlie SSSI. 403 records from Fauna de Caño Cristales, Sierra de La Macarena, Meta - Colombia. 141 records from Observations de mammifères marins issues des campagnes dans les Terres Australes et Antarctiques Françaises (programme 109 Institut Polaire Français - IPEV). 3 records from New species of leaf-mining Nepticulidae (Lepidoptera) from the Neotropical and Ando-Patagonian regions, with new data on host plants. 6 records from On a new species of the rare syllid genus Exogonoides (Annelida, Phyllodocida, Syllidae). 1 records from Description of a new species of the fish genus Acanthoplesiops Regan (Teleostei: Plesiopidae: Acanthoclininae) from Tonga.. 4368 records from RHS berberis sawfly (Arge berberidis) monitoring. 6 records from Dispatch from the field II: the mystery of the red and blue Opadometa male (Araneae, Tetragnathidae, Opadometa sarawakensis). 83 records from Abundance of benthos infauna at station GIK23002-1. 94 records from ANDEEP3: SeaStars (Echinodermata, Asteroidea). 7 records from Natura 2000 Hauts de Meuse, complexe d'habitats éclatés. 1 records from Description of a new species of Hoolock gibbon (Primates: Hylobatidae) based on integrative taxonomy. 1 records from Foraminifera abundance of Hole 48-405. 8 records from Planktic foraminifera abundance of Hole 32-305. 290 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 170 records from Naturschutzstation Schmidsfelden. 340563 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 6 records from A new species of Buenia (Perciformes: Gobiidae) from the western Mediterranean slope bottoms, the redescription of Buenia jeffreysi and the first Balearic record of Buenia affinis. 17053 records from Distribution of 15 major fish species in the North Sea between 1959 and 1979. 81502 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 19242 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. 66 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 3105 records from SPC PROCFish/C Invertebrates Observations Samoa 2005. 32 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 112-683B. 51 records from (Table 3) Distribution of planktonic foraminifers in ODP Site 126-791. 13 records from A new sun moth species from the Flinders Ranges in South Australia (Lepidoptera, Castniidae). 10 records from Nannofossil abundance of Hole 29-283A. 3 records from Nannofossil abundance of Hole 3-14. 132365 records from Dry Tortugas Reef Visual Census 1999. 33963 records from NaGISA Project. 3 records from Revision and phylogeny of the genus Balgus Fleutiaux, 1920 (Coleoptera, Elateridae, Thylacosterninae). 208 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 666 records from BIRDRACE Cuxland - Schwenke Geo Consult. 42 records from Riedkanal Bötzingen. 104 records from Die Wuhle. 148 records from Birdrace_Gätkes_Schergen-Helgoland. 687 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 4 records from A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan. 5781 records from RNF - Données de l'Association GEREPI. 2 records from Ecología y comportamiento de dos carnívoros del Bolsón de Mapimí, Durango. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 6 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 241223 records from Wider Countryside Butterfly Scheme (WCBS). 45 records from Taxonomic notes and faunistic data on the Muscidae (Diptera) of the Altai Mountains (Russia). 595 records from Aves de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 78 records from Nannofossil abundance of Hole 8-73. 65 records from Listhof und Umgebung. 11 records from Distribution of meiobenthos in sediment core M19_263 of the northeastern Atlantic (Table 1). 4 records from Abundance of nematoda in sediment profile M3/1_021 from the Iberian deep sea basin (Table 5). 12 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina – Colección Crocodylia (MFA-ZV-C). 56 records from Museu Paraense Emilio Goeldi - Acari Collection. 341 records from BIRDRACE Die Laufenten. 623 records from BIRDRACE Gätkes Erben. 32 records from Pollen profile from sediment core AV14_K2-1. 9717 records from RECORD Chiroptera Data. 8 records from A new Mapinguari Papavero & Wilcox (Diptera, Mydidae, Mydinae) from Minas Gerais State, Brazil. 302 records from SNH Invertebrate Site Condition Monitoring 2013/14: Lismore Lochs SSSI. 36196 records from River Macrophytes Database. 1383 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 78209865 records from Artportalen (Swedish Species Observation System). 21647 records from National River Water Quality Network Database (Macro-invertebrates). 694 records from Données naturalistes de François BRETON. 37910 records from RECORD Mammal Data. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 345960 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 136 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 1795 records from Données naturalistes de Pascal ROUSSE. 6 records from GreenLogic_2017_12_18. 1876 records from TTRS Mammals. 10 records from Beitrag zur Kenntnis der Oribatiden Mitteleuropas (Neue Liacarus-Arten). 26 records from Description of one new genus and four new species of mynoglenine spiders from Africa (Araneae: Linyphiidae: Mynogleninae). 3 records from Presence of the Glossosomatidae in Madagascar, with description of two species (Trichoptera). 184 records from (Appendix Table 2) Relative abundances of calcareous nannofossil in the >4 µm assemblage of ODP Hole 177-1090D. 8790 records from Inventario de la lepidopterofauna de la Sierra de Huautla. 2566 records from Database of Australasian Vertebrate Occurrences. 192 records from Redlisted beetles found in oak grove near Lake Østensjø. 204 records from Données naturalistes d'Arzhvaël JEUSSET. 150 records from Überall ist Wunderland. 16 records from Analyses of the recent components in the sand fraction of sediment core PS1402-2. 10 records from Absolute abundances of benthic and planktonic foraminifers in samples of ODP Hole 149-901A (Table 1). 19 records from Pollen record of a sediment profile from Lake Teletskoye. 3 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 1314 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE275. 168 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Tanaidacea.. 16 records from A Revision of the Pseudotropheus elongatus species group (Teleostei: Cichlidae) With Description of a New Genus and Seven New Species. 174 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 12 records from Nannofossil abundance of Hole 67-494. 39 records from Ostracod species in Oligocene sediments of core CRP-3. 7842 records from MfN - Fossil invertebrates IIb. 76 records from Microzooplankton abundance measured on water bottle samples at station PS58/012-5. 4 records from First record of the family Stephanidae (Hymenoptera: Stephanoidea) for the fauna of Saudi Arabia, with the description of a new species. 2 records from Phytoplankton abundance at station CD47_0306C#7. 1783 records from ZUEC-CRU - Coleção de Crustacea do Museu de Zoologia da UNICAMP. 62 records from Düpenauwiesen. 11671 records from Mammal assemblages recorded by camera traps inside and outside the evacuation zone of the Fukushima Daiichi Nuclear Power Plant accident. 6 records from Pamphagidae (Orthoptera: Acridoidea) from the Palaearctic Region: taxonomy, classification, keys to genera and a review of the tribe Nocarodeini I. Bolívar. 15 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 163 records from Entomofauna laguna El Tinije. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 872 records from Status, ecología y conservación de loros Amazona en el Noreste de México. 17 records from Collection Crustacea - ZSRO. 2 records from Revision of the genus Sinobathyscia Perreau (Coleoptera, Leiodidae, Cholevinae) from China, with description of a new species. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 246 records from Araignées PNRL-2010 (Troyon,Jezainville-pelouse, Genicourt-pelouse). 6 records from Palaearctic species of Thaumastoptera (s. str.) Mik (Diptera: Limoniidae). 18 records from Zoology (Museum of Evolution - Uppsala). 286 records from Estudio de la distribución geográfica de Peromyscus ochraventer y análisis de su variabilidad cromosómica. 13641 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. 31 records from Crustáceos malacostracos de la cuenca del río Papaloapan, Veracruz. 366 records from Anfibios y reptiles de la cuenca alta y media del río Bita, Vichada (Colombia). 1278 records from Plume moths - ANIC. 13 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Myriapoda National Collection (MACNMy). 102105 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 19 records from The genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae: Syllinae) from Australia (second part): four new species and re-description of twelve previously described species. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 14 records from (Table 3) Benthic foraminiferal genera in DSDP Core 95-612-21-5 and 95-612-21-6. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 17 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña diciembre 2010. 46 records from (Table 6) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841B. 50 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 1 records from Two new genera and two new species of cicadas from Central America (Hemiptera: Cicadidae: Cicadinae). 1046 records from Birds of Cisna Community (southern Poland). 667039 records from DASSH Data Archive Centre - Statutory Surveys. 1 records from Crossing the Indian Ocean: a range extension for Goreopagurus poorei Lemaitre & McLaughlin, 2003 (Crustacea: Decapoda: Paguridae). 9 records from Review of the genus Zeugomutilla Chen, 1957 (Hymenoptera, Mutillidae, Mutillini), with description of two new species. 1734 records from Yorkshire Wildlife Trust Shoresearch. 49041 records from UK Ladybird Survey data from iRecord. 6810 records from Phenological observations of biota on the territory of Prioksko-Terrasnyi biosphere reserve. 241 records from UWIZM Cerambycidae Beetles. 389 records from USGS Alaska Science Center Polar Bear Maternal Dens. 88 records from Phytoplankton abundance at several bottle stations in may 1996, Pisco, Peru. 1 records from Foraminifera abundance of Hole 48-403. 52308 records from PSM Vertebrates Collection. 827 records from Colección de Paleoinvertebrados del IANIGLA-CCT CONICET Mendoza: IANIGLA-PI. 118 records from Occurrence of mammalia relicts at site Istalloskö. 138 records from Schussenaue (Weingarten). 210 records from Tag der Artenvielfalt in der Stadt Luzern. 182 records from Artenvielfalt auf den Elbwiesen (Dessau). 234 records from Antarctic Krill occurrence data from Australian expeditions. 1268 records from Antarctic Krill occurrence data from US AMLR "US Antarctic Marine Living Resources" Program. 5382 records from Elephant Seal Sightings, Heard Island. 4387 records from Environment Agency Eiseniella tetraedra Records (England). 666 records from Límites de especies dentro del género Gerrhonotus (Sauria: Anguidae). 5502 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 4246 records from Diversidad de peces de las lagunas costeras de Pueblo Viejo y el Mango, Veracruz. 58 records from Leaf-mining Nepticulidae (Lepidoptera) from record high altitudes: documenting an entire new fauna in the Andean páramo and puna. 200 records from (Figure 7) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-630A. 3 records from A new stygobiont species of Halocaridinides Fujino & Shokita, 1975 (Crustacea, Decapoda, Caridea, Atyidae) from caves on Socotra Island (Yemen), with notes on the genus. 33 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688E, Part II. 48 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 1443 records from A geographic distribution database of Mononychellus mites (Acari: Tetranychidae) on cassava (Manihot esculenta). 20 records from Nannofossil abundance of Hole 73-521. 98 records from Microfossil abundance of Hole 16-157. 3 records from Nannofossil abundance of Hole 34-321. 43 records from Relative abundance of coccosphere-units of site GIK23259. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 23064 records from Museu Paraense Emilio Goeldi - Hymenoptera Collection. 66 records from Microzooplankton abundance measured on water bottle samples at station PS58/041-2. 64 records from Microzooplankton abundance measured on water bottle samples at station PS58/009-2. 36 records from Microzooplankton abundance and biomass at station TT045_7-13. 220 records from BIRDRACE Angeliter Ornis. 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 298 records from Birdrace-Usedommeln-Ostvorpommern. 64 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 220 records from Birdrace-LiLaMai-Vechta. 158 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 520 records from Macrozoobenthos composition, abundance and biomass in the Arctic Ocean along a transect between Svalbard and the Makarov Basin 1991. 1 records from Range table from benthic foraminifers in ODP Hole 149-898B. 2 records from A new Icimauna Martins & Galileo, 1991, from the Bolivian orocline (Coleoptera, Cerambycidae, Lamiinae, Hemilophini). 60 records from Occurrence of mammalia relicts at site Risovaca. 36 records from Occurrence of mammalia relicts at site Luttenberg. 34 records from Occurrence of mammalia relicts at site Willments Pit. 192 records from Occurrence of mammalia relicts at site Remetehegy. 42156 records from LSUMZ Mammals Collection. 5670 records from Inventaire des Noctuelles de Guyane (Lepidoptera : Euteliidae, Erebidae, Noctuidae, Nolidae). 5 records from Collection Arachnologie fossil - SMF. 12796 records from Fish collection NTNU University Museum. 106941 records from IG TUT paleontology. 4 records from Flatworm specimens of Ryukyu University Museum (Fujukan). 748 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE278. 440 records from Benthic macrofauna abundance of subcores of sediment core 12930-065. 1894 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine. 25 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 1129 records from Monitoreo de la abundancia de juveniles de langosta Panulirus argus como índice de reclutamiento inminente en Sian Ka'an (Reserva de la Biósfera). 657 records from MfN - Fossil vertebrates V. 4 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 32 records from Microzooplankton abundance and biomass at station TT045_26-3. 36 records from Microzooplankton abundance and biomass at station TT045_19-3. 128 records from Distribution of palynomorphs in surface sediments of the Laptev Sea. 5936 records from John Clayton's Fijian Moth Collection. 136 records from FFH-Gebiet Paartal. 25 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 6 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 1332 records from CSIRO, Cruise SS2005007, Benthic Biodiversity, Western Australia, 2007. 31 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 91572 records from Denver Museum of Nature & Science - Entomology. 359 records from Inventaire malacologique du site Natura 2000 FR9301537 de la Montagne de Lure (2002, ONF/MNHN). 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 4 records from New genus of diminutive microhylid frogs from Papua New Guinea. 72 records from Inventaire hivernal des nids de frelon asiatique. 84 records from Estudio poblacional y conservación del mono araña (Ateles geoffroyi yucatanensis) en la región nororiental Península de Yucatán. 5440 records from Conventions d’étude sur la biodiversité française – Partenariats du SPN. 168 records from Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific. 175 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 42 records from (Table AT5) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130A. 11028 records from Mollusc (marine) data for Great Britain and Ireland - restricted access. 33 records from Wanzen_Raw1. 10 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 72 records from Abundance of benthos infauna at station GIK23017-1. 1778 records from Fauna y flora asociada a 18 humedales del valle geográfico del río Cauca. 22 records from Klosterwald Itzehoe. 333 records from Inventaire de l'îlot du Lédénez Vraz. 1 records from Planktic foraminifera abundance of Hole 1-1. 4 records from Planktic foraminifera abundance of Hole 14-136. 128 records from Neogene palynomorpha from site 93-603, part 2. 45 records from Occurrence of mammalia relicts at site Eich. 117224 records from Pacific Ocean Shelf Tracking (OBIS Canada). 8 records from Pycnogonidea specimens of Kuroshio Biological Research Foundation. 12642 records from Los mamíferos del estado de Durango, México. 6624 records from Base de datos sobre ictioplancton para la Bahía de Campeche, México. 8518 records from Literary descriptions of Iranian lizards. 74 records from (Table 8) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-662A. 206 records from Antarctic Nemertea. 86 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 31 records from Projekt Wahner Heide. 5135 records from Jeu de données convention FEGVE-SPN-2012-2016. 50 records from Nannofossil abundance of Hole 37-332A. 4 records from Nannofossil abundance of Hole 10-94. 146 records from Feuerlöschteich, Wald und Dünen in den Holmer Sandbergen. 2 records from Abundance of radiolaria at station LV28-64-2. 2 records from Abundance of radiolaria at station LV28-4-1. 8 records from Distribution of meiobenthos in sediment core M19_216-2 of the northeastern Atlantic (Table 1). 78 records from Microzooplankton abundance measured on water bottle samples at station PS58/046-3. 261 records from Inventaire 3B initié par l'Université de Bordeaux 2012 / 2014. 36 records from Microzooplankton abundance and biomass at station TT043_29-1. 44 records from Concentration of siliceous microplankton in surface sediments, size fraction > 40 µm. 28 records from Abundance of microzooplankton measured on water bottle samples during METEOR cruise M17/1. 285 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 30 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 4 records from Sächsische Schweiz (Wehlener Gebiet). 26 records from Mittelriede Höhe Gliesmarode-Braunschweig. 32 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 1 records from A new species of Caligus Müller, 1785 (Copepoda: Siphonostomatoida: Caligidae) from coral reef plankton in the Mexican Caribbean. 1 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 60 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 3375 records from NMMNH Mammal. 19 records from Données naturalistes d'Océane ROQUINARC'H. 24 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 118 records from El rorcual común Balaenoptera physalus, en el Golfo de California, México. 236 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 91 records from Biological Recording in Scotland - New Zealand Flatworm Survey. 1 records from University of Lethbridge Herbarium (LEA). 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 61 records from Shrews of Poland. 1008 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 908 records from IPOE_Benthos_Steffens. 4 records from Données naturalistes de Lionel PICARD. 22 records from Données naturalistes d'Alain MIGEON. 8332 records from Scotland Otter Survey Database. 3182 records from CHAS Oology Collection (Arctos). 6699 records from SEWBReC Myriapods, Isopods, and allied species (South East Wales). 5 records from Phonognatha vicitra Sherriffs, 1928 - a taxonomic misidentification of the orb-weaving spider Acusilas coccineus Simon, 1895 (Araneae, Araneidae). 5439 records from CSIRO, Fish Survey, Albatross Bay - Gulf of Capentaria, North Australia, 1986-1988. 151 records from Macrofauna abundances from mesocosm experiments at eastern and western branches of the Whittard canyon. 9 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 2548 records from BioGIS - Reptiles - HUJ collections. 44 records from A survey of spider taxa new to Israel (Arachnida: Araneae). 2 records from A new species of the genus Discoelius Latreille, 1809 (Hymenoptera: Vespidae: Eumeninae) from India. 371 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 1 records from Range table from benthic foraminifers in ODP Hole 145-887C. 4083 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 1 records from Foraminifera abundance of Hole 60-453. 2759 records from Données naturalistes de Jean-Hervé YVINEC. 9 records from Planktic foraminifera abundance of Hole 29-281. 81 records from Distribution of major planktic foraminifer at Site 177-1088. 66 records from Occurrence of mammalia relicts at site Stellmoor. 110 records from Überschwemmungsgebiet der Wied. 1756 records from GEO-Hauptveranstaltung (Duisburg). 46408 records from KWP Lepidoptera Collection (Arctos). 128 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 4957 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB05 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 122 records from Knechtweide (Kohlfurth). 2720 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 6 records from (Appendix 1) Late Cretaceous benthic foraminifera of ODP Hole 207-1257A. 493 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE241. 291 records from SuLaMa reptile survey 2013. 292 records from (Table 2) Expected and observed beluga (Delphinapterus leucas) sightings according to habitat characteristics. 6 records from Collection Cnidaria - ZIM Hamburg. 274269 records from IZIKO South Africa Museum Collection (1800-2013). 18 records from CSD_ingénieurs_2017_12_18. 4 records from Regenwasserabfangbecken Erlenbach. 204 records from BIRDRACE HGON Kelkheim-Rumpfteam. 37092 records from ICN - Universidad Nacional de Colombia. 107 records from The Psylloidea (Hemiptera) of Israel. 145 records from Nannofossil abundance of Hole 67-497. 62 records from Nannofossil abundance of Hole 60-458. 4 records from Nannofossil abundance of Hole 31-300. 14 records from Nannofossil abundance of Hole 9-79. 1333 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 8332 records from Projet SYRFID 2 (données bibliographiques sur les Syrphes de France). 42 records from Review of Namibimydas Hesse, 1972 and Nothomydas Hesse, 1969 (Diptera: Mydidae: Syllegomydinae: Halterorchini) with the description of new species. 22 records from Biological data measured on water bottle sampels at station AT_II-119/5_38-5. 1434 records from UWIZM Scarabaeidae Beetles. 24 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 12 records from Strongly carinate species of Alpheopsis Coutière, 1897 of the tropical Atlantic and eastern Pacific, with redescription of A. trigona (Rathbun, 1901) and description of three new species (Malacostraca: Decapoda: Alpheidae). 234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 983 records from Modernisation 2009-2012 des ZNIEFF de Guyane. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 5 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 10738 records from Bringing Reedbeds to Life Invertebrate Survey of three key reedbed sites in England in 2009, 2010. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 2091 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 15587 records from Bedfordshire Mollusca (Non-sensitive) (BNHS) - 1940-1994. 4 records from A new species of Protaetia Burmeister, 1842 from Armenia with taxonomic notes on Cetonia floricola fausti Kraatz, 1891 (Coleoptera: Scarabaeidae: Cetoniinae). 1969 records from Colección de Mamíferos del Instituto Alexander von Humboldt. 1 records from First record of the Mouse-colored Tyrannulet, Phaeomyias murina (Spix, 1825) (Aves, Tyrannidae), for Rio Grande do Sul, Brazil. 8 records from First record of Naushonia sp. (Decapoda: Laomediidae) larva from the Equatorial Atlantic. 8 records from Colección de Referencia de Urocordados del Museo de Ciencias de la Universidad El Bosque. 3 records from PRECIS. 33 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 536 records from Woodland Survey. 91077 records from Oregon State University Herpetological Collection. 18121 records from Insectes Lépidoptères Rhopalocères de France métropolitaine. 3239 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 111 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 88621 records from UAIC Ichthyological Collection. 2 records from Two new genera of predatory katydids (Orthoptera: Tettigoniidae: Meconematinae) from the Amazon rainforest. 778 records from Bird specimens of Saitama Museum of Natural History. 399 records from Macrofauna edáfica de ecosistemas asociados a la cuenca hidrográfica del río Orotoy, Meta. 1284 records from Données naturalistes de Thomas LORICH. 60 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 9 records from Revision of the Old World Daphnia (Ctenodaphnia) similis group (Cladocera: Daphniidae). 2898 records from DBL_Life. 25057 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 2 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 25 records from Planktic foraminifera abundance of Hole 17-165A. 2 records from Cactodera chenopodiae (Nematoda: Heteroderidae), a new species of cyst nematode parasitizing common lambsquarter (Chenopodium album) in Liaoning, China. 590 records from Aves Bosque Seco Chicamocha. 64 records from Occurrence of mammalia relicts at site Kesslerloch. 142 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 2 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 66324 records from UCLA Donald R. Dickey Bird and Mammal Collection. 40 records from Animal observations. 51025 records from Partial Amphibians Collection. 43 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Fitoplancton de lagos pirenaicos. 446 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-708A. 4 records from (Table 3) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-754A. 18 records from (Table 2) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Site 121-756. 614052 records from Florida Keys Reef Visual Census 2011. 111 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 172 records from Antarctic Parborlasia corrugatus. 20 records from Benthic macrofauna abundance of sediment core 13077-023. 71 records from Cabinet_Barbanson_Environnement_2017_12_18. 44 records from Nannofossil abundance of Hole 4-29B. 32 records from Nannofossil abundance of Hole 6-47B. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 164 records from Juvenile scalloped hammerhead sharks in the Rewa River estuary, Viti Levu, Fiji 2012. 253 records from Mosquitoes (Culicidae) of Ireland. 58 records from Schulgarten Zinnowwald-GS. 150 records from BIRDRACE Die Kartoffelsäcke. 22 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 106 records from Bad Bodenteicher Heide. 72 records from Neanderthal. 2 records from La liste Rouge des plantes menacées de la Guinée (BID-AF2015-0042-NAC). 106 records from Projet Diable de mer - AILERONS. 420 records from Données naturalistes de l'AGUPE (Association Générale d'Urbanisme et de Protection de l'Environnement). 391 records from Crustacea collection of the Finnish Museum of Natural History. 23 records from Gare impérial de Chambrey-FDFR 57. 71595 records from Seasearch Marine Surveys in Wales. 3878 records from East Ayrshire Species Database. 6 records from Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela). 72 records from Pollen record of sediment core Bokanjacko Blato 1. 8312 records from Southern Ocean octopus. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 14 records from Grundschule Sandheide. 714941 records from LACM Vertebrate Collection. 35 records from Benthic macrofauna abundance of sediment core 13200-047. 38 records from Meiofauna abundance in sediment core 13368-003. 28 records from Nannofossil abundance of Hole 5-32. 5 records from Nannofossil abundance of Hole 5-37. 21 records from Coccoliths in sediment core PS1295-4. 5 records from Distribution of meiobenthos in sediment core M23_149 of the northeastern Atlantic (Table 1). 88 records from Microzooplankton abundance measured on water bottle samples at station PS58/011-1. 846 records from Mol·luscs d'Andorra. 62 records from Faunal assemblage of sediment core TR149-38b. 16 records from VFD-RP: Taunus: Ponykoppel Thurner. 18135 records from Merseyside BioBank Active Naturalists (unverified). 46 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 3530 records from Dorset SW Pilot species dataset. 25460 records from PPEAO - Pêches scientifiques. Peuplements de poissons des écosystèmes estuariens, lagunaires et continentaux d'Afrique de l'Ouest. 886 records from Jeu de données convention CD78-SPN-2014-2015. 4857 records from Fauna carcinológica de México. Crustáceos estomatópodos y decápodos del Golfo de México. Río Bravo, Tamaulipas a Cabo Catoche, Q.Roo. 7402 records from Helgeland Museum, Lepidoptera. 6 records from New Siberian “ spineless ” species of Thalassaphorura Bagnall, 1949 (Collembola, Onychiuridae), with a key to world species of the genus. 21750 records from Observations de mammifères marins du Réseau National d'Echouages en Métropole. 26812 records from Données Opie, Coléoptères saproxyliques. 2 records from New genus and species of brachypterous planthopper of the tribe Elicini (Hemiptera: Fulgoroidea: Tropiduchidae) from Chile. 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 27666 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 54 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 2 records from Palaearctic Hoplitis bees of the subgenera Formicapis and Tkalcua (Megachilidae, Osmiini): biology, taxonomy and key to species. 10217 records from RECORD Aculeate Hymenoptera Data. 1904 records from Flickr (01) Shieldbugs & allied species. 2 records from (Table 2) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-198A. 4 records from Prosorhynchus Odhner, 1905 (Digenea: Bucephalidae) from the orange-spotted grouper Epinephelus coioides (Hamilton, 1822) (Epinephelidae), including Prosorhynchus tonkinensis n. sp., from the Gulf of Tonkin, Vietnam. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 17252 records from DREAL_PACA_-_N2000_-_SMIGIBA_2017_12_18. 165 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 10981 records from Catalogue of Afrotropical Bees. 23 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 497 records from Données naturalistes de Guilène PROCIDA. 12828 records from Talvik fish tag database. 110 records from Contribution to the knowledge of meiobenthic Copepoda (Crustacea) from the Sardinian coast, Italy. 67 records from Collection Coleoptera SMF. 39905 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 426 records from Occurrence of mammalia relicts at site Gare de Couze-Serie 2. 21 records from Occurrence of mammalia relicts at site Beckford. 2 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV22. 4 records from The ant genus Tetraponera in the Afrotropical region: the T. grandidieri group (Hymenoptera: Formicidae).. 6011 records from globec/soglobec/process/krill. 7322 records from Leicestershire and Rutland Diptera. 36 records from (Table 4) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897D. 47 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 2 records from Specimens of Phylum Porifera of Akita Prefectural Museum. 1354 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 38 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688E, Part I. 4 records from (Table 1) Distribution of benthic foraminifers in ODP Hole 107-650A. 17650 records from Rådgivende Biologer. 4 records from Range table from ostracoda in ODP Hole 159-960A. 451 records from Nannofossil abundance of Hole 58-445. 2 records from Redescription of Urophycis brasiliensis (Kaup 1858), a senior synonym of Urophycis latus Miranda Ribeiro 1903 (Gadiformes: Phycidae). 15 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/314-1. 195 records from Bird specimens of Obihiro Centennial City Museum. 6 records from Schulhof Liebfrauenschule Oldenburg. 80 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 218 records from Birdrace-Team_Charadrius-Günzburg. 7170 records from Marine Turtles. 24 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 5 records from The Cephenniini of China. VIII. New species and new records of Cephennodes Reitter of Hunan, Jiangxi, Zhejian and Fujian (Coleoptera: Staphylinidae: Scydmaeninae). 102 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 1 records from Notes on Cataglyphis Foerster, 1850 of the bicolor species-group in Israel, with description of a new species (Hymenoptera: Formicidae). 393 records from Danish Lacewings (Neuroptera). 8747 records from Inventario de la fauna arrecifal asociada al ecosistema de Pocillopora en el Pacífico Tropical Mexicano. 239 records from Rutilans. 706367 records from Fishbase. 23 records from New species and synonymies in Xenopygus Bernhauer (Coleoptera: Staphylinidae: Staphylinini). 218 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 4426 records from HBRG P.F. Entwistle Insects Dataset. 290016 records from Western Australia Bird Surveys (1987-2015). 16012 records from Knerer collection / Gschwendtner property. 4 records from Two new species of Haploperla (Plecoptera: Chloroperlidae) from China. 182 records from Mammal specimens of Saitama Museum of Natural History. 4 records from Miscellaneous Vascular Plants. 2 records from Paläoherpetologie - SMF. 3 records from Données naturalistes (hors araignées) de Claire JACQUET. 246 records from NMNH Paleobiology Specimen Records. 20 records from Limonia crane flies (Diptera: Limoniidae) of Korea. 1102 records from New Zealand Flatworm (Arthurdendyus triangulatus) records for Scotland 2008-2014. 10 records from New or little-known species of Chaetocladius s. str. Kieffer, 1911 (Diptera: Chironomidae: Orthocladiinae) from the Amur River basin (Russian Far East). 342 records from SNH Invertebrate Site Condition Monitoring 2015-16: Methven Woods SSSI. 10 records from Two new species of Coelostoma Brullé, 1835 from China and additional faunistic records of the genus from the Oriental Region (Coleoptera: Hydrophilidae: Sphaeridiinae: Coelostomatini). 3 records from A new species of the genus Rhynchocalamus Günther, 1864 (Reptilia: Squamata: Colubridae) from Ilam province in western Iran. 4586 records from NORFANZ Biological Survey, Tasman Sea, Australia - New Zealand 2003. 1 records from Four new species of the genus Mannerheimia Mäklin, 1880 (Coleoptera: Staphylinidae: Omaliinae) from south-western China and Taiwan. 5 records from A new species of Physalaemus (Anura, Leptodactylidae) from the Atlantic Forest of Misiones, northeastern Argentina. 1 records from First finding of the shrimp genus Harperalpheus Felder & Anker, 2007 in the eastern Pacific, with description of a new species from Bahía Málaga, Colombia (Malacostraca: Decapoda: Alpheidae). 1286 records from Conservación de la guacamaya verde (Ara militaris) en la Reserva de la Biósfera Tehuacán-Cuicatlán, México: un estudio de abundancia y reproducción en la zona de la cañada. 80 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 372 records from Bergkamen- Bergehalde Großes Holz. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 1 records from Micropygomyia (Coquillettimyia) nahua sp. nov., a new Phlebotominae sand fly from Mexico (Diptera, Psychodidae). 234 records from Various insect orders, NEF. 15306 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 425 records from GCP_2017_12_18. 34 records from Sipuncula collection of National Museum of Nature and Science. 1 records from Spelaeogammarus uai (Bogidielloidea: Artesiidae): a new troglobitic amphipod from Brazil. 374 records from UWIZM Mammals. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 2061000 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 4 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 20294 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 100 records from Status, distribución, ecología y conservación de las cotorras serranas (Rhynchopsitta pachyrhyncha y R. terrisi) en el norte de México. 313 records from VIP topsoil data jointsampling soilfauna, 2008. 761 records from Fauna acuática de importancia ecológica (crustáceos, insectos y peces) de la cuenca del río Moctezuma Querétaro-Hidalgo. 10 records from Systematic and taxonomic observations on the subfamily Synapseudinae Guţu, 1972 and related metapseudid taxa (Crustacea: Tanaidacea: Apseudomorpha), with the erection of a new genus and descriptions of three new species. 3 records from A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae). 6164 records from Antarctic, Sub-Antarctic and cold temperate echinoid database. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 54 records from Données "faune" de LABBAYE Olivier pour le SINP île de France. 19 records from New Linyphiidae spiders associated with playas in the Southern High Plains (Llano Estacado) of Texas (Arachnida: Araneae). 3 records from A new species of Scinax Wagler (Anura: Hylidae) from Paraná, Southern Brazil. 27 records from New taxa of the mite family Neopygmephoridae (Acari: Heterostigmata) from alpine New Zealand. 8352 records from Badger and Habitats Survey of Ireland. 51 records from Dichte_Arion_rufus.xls. 374 records from Biología reproductiva y diversidad genética: hacia el conocimiento integral del murciélago pescador Myotis vivesi. 22 records from Auenwiesen und Trockenrasen. 18 records from Observation of birds at station PS14/151 along 49° West. 1 records from Giant among dwarfs: Meganannus lewisi, gen. n. and sp. n., a new genus and species of minute litter bugs from Costa Rica (Hemiptera: Schizopteridae). 8 records from Planktic foraminifera abundance of Hole 14-139. 98 records from Occurrence of mammalia relicts at site Jaskinia Niedwiedzia. 28 records from New species and phylogenetic relationships of the spider genus Coptoprepes using morphological and sequence data (Araneae: Anyphaenidae). 153 records from Meiobenthic assemblages colonizing artificial soft sediments at 20 m depth in Arctic glacial Kongsfjorden, Spitsbergen, Svalbard - individual number. 266 records from Benthic foraminiferal abundances at the Cretaceous/Paleogene boundary of ODP Hole 117-1049C at Blake Nose, Northwest Atlantic (Appendix A). 816 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 26 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 30 records from Die geheimnisvolle Welt der Spinnen. 192 records from Birdrace-Berlin_Sparrows-Uckermark. 217144 records from National Trust Species Records. 34 records from Broch H. 1935. The fishery grounds near Alexandria. III Cirripeds. Notes et Memoires No 10.. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 23 records from Taxonomic revision and cladistic analysis of the genus Metalibitia Roewer, 1912 (Opiliones, Cosmetidae, Cosmetinae). 281 records from Ecología e historia natural de Schistocerca americana socorro y S. piceifrons piceifrons en Isla Socorro. 76 records from Harant H. 1939. Les fonds de peche pres d'Alexandrie. Ascidiacea (Cartes 1-5). Notes et Memoirs No 28. Institut fouad 1er d' Hydrobiologie et de peche, Egypt. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 21204 records from Danish Plant Bugs (Miridae). 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 9 records from Squalius semae, a new species of chub from the Euphrates River, Eastern Anatolia (Teleostei: Cyprinidae). 1259 records from Paläontologie Marburg. 31885 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 2 records from Characterization of Platymessa with redescription of the type species and a new generic synonymy (Arachnida, Opiliones, Cosmetidae). 20 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 48 records from The New Zealand triplefin Grahamina signata (Teleostei; Tripterygiidae): A junior synonym of G.gymnota from Tasmania. 7 records from (Table 3) Concentrations of brominated flame retardants in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 1460 records from Coleoptera of Kozienice Forest. 44642 records from The Fish Database of Taiwan. 24970 records from Heteroptera: Records for Kent. 125 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 493 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 6458 records from Anfibios y reptiles del estado de Tamaulipas, México. 230 records from NE Scotland Wildcat records 1800-2011. 988 records from Occurrence of mammalia relicts at site Raj Cave. 864 records from Erlengraben/Lipp-Tal (Östringen). 1778242 records from Hawk Migration Association of North America - HawkCount. 24 records from (Table 3) Benthic foraminifera in early-middle Miocene sediments of DSDP Site 89-586. 276 records from Birds Specimens of Akita Prefectural Museum. 22 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-13. 59 records from (Table 3) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-647A. 1868 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 18 records from Range table from nannofossils in ODP Hole 139-855A. 10 records from Nannofossil abundance of Hole 11-105. 43 records from Ostracoda abundance of Hole 11-105. 44 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 94014 records from TNHC Ichthyology Collection. 40 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 22 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 63 records from Mamíferos, aves y peces de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 1185 records from MCNH Museum of Cultural and Natural History Reptile Collection. 4240 records from Crustacea collection of National Museum of Nature and Science. 272 records from Inventaire de la faune malacologique de la Réserve naturelle des gorges de l'Ardèche (2002). 5 records from A taxonomic review of Korean Liogluta Thomson (Coleoptera, Staphylinidae, Aleocharinae) with descriptions of three new species. 1 records from A new sexually dichromatic species of Telenomus Haliday (Platygastroidea: Scelionidae) from India. 68 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 2 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 160 records from New species of the damselfly genus Argia from Mexico, Central America and Ecuador with an emphasis on Costa Rica (Insecta: Odonata: Coenagrionidae). 23 records from Overview of the Anyphaenids (Araneae, Anyphaeninae, Anyphaenidae) spider fauna from the Chocó forest of Ecuador, with the description of thirteen new species. 10 records from New contributions to the knowledge of Chinese flea beetle fauna (III): revision of Meishania Chen & Wang with description of five new species (Coleoptera: Chrysomelidae: Galerucinae). 7 records from Euastacus vesper sp. nov., a new giant spiny crayfish (Crustacea, Decapoda, Parastacidae) from the Great Dividing Range, New South Wales, Australia. 6 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 6 records from Collection Myriapoda - SNSD. 874 records from Gaïadomo_2017_12_18. 1 records from Review of the Paratydeidae (Acari: Prostigmata), with description of three new species. 1 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 1403 records from La Planète Revisitée, mission complémentaire entomologique, massif du Mitaraka, août 2015. 3 records from On the taxonomy of Korean jumping plant-lice (Hemiptera: Psylloidea). 194 records from Moorea Biocode : Mollusques terrestres et aquatiques. 4 records from Redescription of Pseudotropheus livingstonii and Pseudotropheus elegans from Lake Malaŵi, Africa. 98 records from SuLaMa Microcebus griseorufus occurence data. 3 records from A newly recognised Australian endemic species of Austrolecanium Gullan & Hodgson 1998 (Hemiptera: Coccidae) from Queensland. 14 records from Additions to the Encyrtidae and Mymaridae (Chalcidoidea) of India with new distribution and host records for some species. 1704 records from Données naturalistes d'Anita GEORGES. 4 records from One new genus and three new species of deep-sea nematodes (Nematoda: Microlaimidae) from the Southwest Pacific Ocean and Ross Sea. 6 records from Description of two new species of Lithoxus (Hypostominae: Loricariidae) from rio Jari and rio Amapá basins, Brazilian Guiana Shield. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 125 records from Données naturalistes de Christian KERBIRIOU. 55 records from Vertebrate Paleontology Division, Yale Peabody Museum. 2 records from Range table from planktonic foraminifers in ODP Hole 182-1132B. 95 records from Foraminifera abundance of Hole 61-462. 6 records from Foraminifera abundance of Hole 18-176. 156 records from Schule Sulzbach (Oberegg). 10 records from Analyses of the recent components of sediment core PS1403-1. 101 records from CNAN/Escorpiones Estado de Mexico. 1401 records from Syndicat_Mixte_du_Massif_des_Monges_2017_12_18. 2 records from Specimens of Class Pycnogonida of Akita Prefectural Museum. 288 records from Nathusius' Pipistrelle Survey. 16 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 36 records from Meiofauna abundance in sediment core 12930-029. 1 records from The Rhyacophila fasciata Group in Western Europe: Confirmation of Rhyacophila denticulata McLachlan 1879 (stat. prom.) and Rhyacophila sociata Navás 1916 (stat. res.), based on morphological and molecular genetic evidence (Trichoptera: Rhyacophilidae). 10331 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 2810 records from Las colecciones del Museu Valencià d'Història Natural. 324 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 2620 records from Distribución, abundancia y riqueza específica de la avifauna terrestre en la Isla Espíritu Santo, Baja California Sur, México. 1547 records from Alterra (NL) - Entomofauna inventory in Speulder forest. 3529 records from (Table 18) Distribution of ostracode species in Core PS51/154-11. 1 records from Filling the gap of whip spider distribution in Asia: Phrynichus persicus sp. n. (Arachnida, Amblypygi), a new Phrynichidae from Iran. 200 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE233. 45 records from (Table 2A) Neogene distribution of calcareous nannofossils at DSDP Hole 43-382. 29 records from Meiofauna abundance in sediment core 12930-015. 2 records from A new species of Charissa Curtis, 1826 from Europe (Lepidoptera: Geometridae). 2 records from Taxonomic review of the genus Commatarcha Meyrick (Lepidoptera: Carposinoidea: Carposinidae) from China, with descriptions of four new species. 2 records from Nannofossil abundance of Hole 7-62. 5 records from Nannofossil abundance of Hole 6-48A. 162 records from Ostracoda abundance of Hole 24-237. 9 records from Ostracoda abundance of Hole 13-134. 37 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 86 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 90 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 2 records from A new species of Isoperla Banks (Plecoptera: Perlodidae) from the northeast of the Russian Far East. 30 records from Bodentiere rund um die Schule. 110 records from FNL e.V.. 208 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 216 records from Mariposas de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 1 records from Typhlocarcinus kerala, a new species of rhizopine crab from southwestern India, and the identity of T. craterifer Rathbun, 1914 (Crustacea: Brachyura: Pilumnidae). 14 records from Two new paratanaid Tanaidacea (Crustacea: Malacostraca: Peracarida) from the Hawaiian Islands, with illustrated taxonomic keys. 3 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. IV. Alopoglossidae, Gymnophthalmidae. 8 records from Ensigeropus, a new genus of the family Platyischnopidae (Amphipoda: Amphilochidea) from Northern Chile. 67 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 2366 records from Modernisation des ZNIEFF du PnrL. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 48980 records from Plan de vertebrados de la Patagonia. 5400 records from smavd_2017_12_18. 108 records from Fishes from Madagascar Reef, Campeche Bank, México. 74 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 17332845 records from Anillamiento SEO_Bird ringing. 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 198 records from Sauvegarde de la flore menacée de l'atoll soulevé de Anaa et définition de zones prioritaires de conservation basées sur la flore et la faune : données sur les Mollusques terrestres et aquatiques. 11 records from Collection Ephemeroptera - SMF. 70 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 3106 records from NatureShare. 2 records from Two species of Cleonini new for Pakistan and new synonymies (Coleoptera: Curculionidae: Lixinae). 451 records from Códigos de barras de helmintos de anfibios y reptiles de México. 3 records from First record of Eggplant Mealybug, Coccidohystrix insolita (Hemiptera: Pseudococcidae), on Guam: Potentially a major pest. 1596 records from Pollen analysis of sediment profile MU1 from Muggesfelder See. 69185 records from BioGIS - Birds - INPA database. 36 records from Abundance of benthos infauna at station PS1239-1. 465264 records from Texas A&M University Insect Collection. 144 records from Ostfriesland. 8 records from Range table from benthic foraminifers in ODP Hole 146-888B. 2 records from Range table from benthic foraminifers in ODP Hole 198-1211B. 8 records from Foraminifera abundance of Hole 64-480. 3 records from Occurrence of mammalia relicts at site Hollerup. 8 records from Nannofossil abundance of Hole 66-489. 36 records from Nannofossil abundance of Hole 30-285. 92 records from Prospections "chevêche". 19 records from Distribution Data for Megachile chomskyi. 31 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 5 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 278 records from BIRDRACE Turbine Untersee. 214 records from Regenrückhaltebecken (Zeulenroda). 1564 records from Pollen analysis of sediment profile WO1 from Wollingster See. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 671400578 records from EOD - eBird Observation Dataset. 4 records from A review of the ant genus Harpegnathos Jerdon, 1851 (Hymenoptera: Formicidae) in the Philippines, with the description of two new species. 100 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 39872 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Bag Seine. 292 records from AGIR_Ecologique_2017_12_18. 9532 records from Evaluación estacional de la fauna ictiológica, malacológica y flora ficológica de la Reserva de la Biósfera El Vizcaino, BCS, Fase I: Laguna Ojo de Liebre. 246 records from Collection Pisces - KAUMM. 37 records from Comunidad de Macroinvertebrados de un Área Degradada por Actividad Minera en la Costa Caucana. 7 records from Description of Paraceto gen. n. and a relimitation of the genus Cetonana (Araneae: Trachelidae). 2723 records from Vleermuiskasten.nl - Bats in bat boxes in The Netherlands and Belgium. 781 records from Bittern Annual Surveys in Britain 1990-2011. 62428 records from Microlepidoptera of Glamorgan. 100 records from Données naturalistes d'Alexandre LERCH. 114 records from Données naturalistes de Marine LEGRAND. 5 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 174 records from (Figure 6) Planktonic foraminifera distribution in ODP Hole 130-803D. 452 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI. 5 records from Taxonomic review of the plant bug subfamily Isometopinae for Taiwan and Japanese Southwest Islands, with descriptions of new taxa (Hemiptera: Heteroptera: Miridae: Isometopinae). 2 records from (Table 3) Benthic foraminiferal composition at DSDP Hole 84-565. 42 records from Tag der Artenvielfalt mit SchülerInnen des Europa-Gymnasiums in Wörth am Rhein. 7 records from Range table from planktonic foraminifers in ODP Hole 154-929E. 3 records from Planktic foraminifera abundance of Hole 63-470A. 232 records from Umgebung der Gesamtschule Hamburg-Winterhude. 1768 records from Invertebrate survey, Heard Island 2001. 105 records from Suivi STERF EcoGIS. 498 records from The Danish Newt Collection. 1628 records from Agriculture and Agri-Food Canada, St. Johns, Newfoundland. 211080 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 58 records from Données naturalistes de Pascal AMBLARD. 956 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE278. 45364 records from BANDASCA, BAse de DAtos sobre SCArabaeidae. 45 records from (Table 4) Acari abundance in control and warming plots, Abisco Research Station. 26 records from Nannofossil abundance of Hole 5-34. 53 records from Schloss Fasanerie Eichenzell. 2 records from Kleinod unter Hochspannung. 221 records from BIRDRACE Die Schwenker-Birder. 16 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 2203 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 708 records from FFH-Gebiet "Calwer Heckengäu". 26 records from Garten Hamburg Uhlenhorst. 54 records from Bolzplatz. 3 records from Taxonomic status of Tropiocolotes cf. steudneri with a description of a new species of Tropiocolotes (Reptilia: Squamata: Gekkonidae) in southern Iran. 3 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 11 records from Données de Lépidoptères de Bruno DAUGET - Dépt du LOIR-ET-CHER (41). 5 records from A mountain of millipedes VI. New records, new species, a new genus and a general discussion of Odontopygidae from the Udzungwa Mts, Tanzania (Diplopoda, Spirostreptida, Odontopygidae). 27353 records from RECORD Odonata Data. 10620 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 87143 records from Sheffield Bird Study Group (Yorkshire records). 146 records from Megophthalmidia_of_North_America. 1 records from Parmaturus nigripalatum n. sp., a new species of deep-sea catshark (Chondrichthyes: Carcharhiniformes: Scyliorhinidae) from Indonesia. 16 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 2 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 19 records from A review of the Subtribe Lebiina Bonelli (Lebiini, Carabidae, Coleoptera) from Southwest of Saudi Arabia. 2718 records from Polychaetes from two subtidal rocky shores of the North coast of Crete, collected for the NaGISA project 2007-2008. 607109 records from Shropshire Ecological Data Network database. 2000 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 286 records from Coastal and Marine Species Database. 4 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 3 records from MSB Mammal Observations (Arctos). 11165 records from SEWBReC Hemiptera - True Bugs (South East Wales). 2 records from Genetic and morphological evidence for a new cryptic species of Ectinogonia (Coleoptera: Buprestidae) from central Chile. 18 records from A new species of the catfish genus Cordylancistrus (Siluriformes, Loricariidae) from the Sierra Nevada de Santa Marta, Colombia. 12 records from A comprehensive checklist of earthworm species and subspecies from Vietnam (Annelida: Clitellata: Oligochaeta: Almidae, Eudrilidae, Glossoscolecidae, Lumbricidae, Megascolecidae, Moniligastridae, Ocnerodrilidae, Octochaetidae). 82 records from Site Condition Monitoring of Annex II Vertigo species in Scotland. 15 records from Porcupine Ray Hunt Data. 4 records from Four new species of the genus Philanthaxia Deyrolle, 1864 (Coleoptera: Buprestidae: Thomassetiini). 12 records from Two new and one redescribed species of Acanthobothrium (Cestoda: Onchoproteocephalidea: Onchobothriidae) from Dasyatis akajei (Myliobatiformes: Dasyatidae) in the China Sea. 21 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 3 records from A new species of the lizardfish genus Synodus (Aulopiformes: Synodontidae) from the western Pacific Ocean. 249 records from données naturalistes de ALZIAR Gabriel. 9900 records from Cumbria Non Native Invasive Species. 2 records from Agence_MTDA_2017_12_18. 3 records from A new species of Pseudobagrus (Teleostei: Siluriformes: Bagridae) from southern China.. 1213 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar1. 20347 records from Animal Sound Archive. 861 records from Floral visits on plants, InsectScale 2008. 30 records from (Table 3) Distribution of foraminifera in the Miocene section of ODP Hole 133-816B. 144 records from Naturpark Drömling. 6 records from Tertiary benthic foraminifera abundance of Hole 95-612. 238 records from Occurrence of mammalia relicts at site Einhornhöhle. 13 records from Occurrence of mammalia relicts at site Endingen. 345 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 218 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 2 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 1 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 86 records from Pollen profile from Samerberg 2. 12087 records from Computarización de la Colección Nacional de Peces del Instituto de Biología UNAM. 218 records from In situ observations of Stygiomedusa gigantea. 927 records from BioBlitz Barcelona 2010-14. 1 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 3095 records from Inventaire des Scléractiniaires de Mayotte. 5 records from Nannofossil abundance of Hole 58-442. 3 records from Nannofossil abundance of Hole 1-4. 14 records from Nannofossil abundance of Hole 16-155. 1363 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 1 records from MfN - Fossil plants (Cenophytic). 4 records from Abundance of radiolaria at station LV28-66-1. 121 records from Caracterización de fauna terrestre y aves de la cuenca del Río Acacías. 2796 records from Données naturalistes de Michel BREUIL. 40 records from Microzooplankton abundance and biomass at station TT045_17-2. 51 records from (Appendix B) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1105-4. 48 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 174 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 1 records from The weevil genera Nyphaeba Pascoe and Pantiala Pascoe and the problems of an unstable nomenclature in orphaned taxa. 27 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 59382 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 1 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 2 records from Two New Variegated Snailfishes of the Genus Careproctus (Teleostei: Scorpaeniformes: Liparidae) from the Aleutian Islands, Alaska. 1 records from Description of Dryocosmus destefanii new species (Hymenoptera: Cynipidae: Cynipini) from Quercus suber L. in Italy. 200 records from Zoological collection of the National Museum. 370 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13 records from A new species of the genus Scybalocanthon (Coleoptera, Scarabaeidae, Scarabaeinae) from the Atlantic rainforest, with an identification key to the species from South America south of the Amazon basin. 938 records from Seasonal dynamics of sub-ice fauna below pack ice in the Arctic (Fram Strait). 9 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 48 records from Fauna herpetológica de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 5 records from New species of Tomocerus (Entomobryomorpha, Tomoceridae) with remarkable form of mucronal dorsal lamella. 3948 records from PINK - Amphibia monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 1 records from Etmopterus lailae sp. nov., a new lanternshark (Squaliformes: Etmopteridae) from the Northwestern Hawaiian Islands. 965 records from Norwegian freshwater lake fish inventory. 2 records from LEXEY RESHCHIKOV & ILARI EERIKKI SÄÄKSJÄRVI (2015) Seven new species of the genus Physotarsus Townes 1966 (Hymenoptera, Ichneumonidae) from South America. Zootaxa, 3972 (1): 026 - 042.. 168380 records from Invertebrate Common Standards Monitoring and ISIS Test Data. 1516 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 3 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 1 records from A new species of the genus Xysticus C. L. Koch from Turkey (Araneae: Thomisidae). 2 records from New Zealand Biodiversity Recording Network. 2853 records from Fauna y flora del municipio de Lipa, Arauca. 142 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 4220 records from Orthoptera (and allies) records for Dumfries and Galloway.. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 419 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 1831 records from Formicidae Collection Univesity of Granada. 2109 records from Harvestmen (Opiliones) of Ireland. 5295 records from PNR_Alpilles_2017_12_18. 2 records from Two new species of the genus Macromotettix Günther, 1939 (Orthoptera: Tetrigidae, Metrodorinae) from China, with a key to the species of the genus. 1 records from Range table from planktonic foraminifers in ODP Hole 146-891A. 34 records from Planktic foraminifera abundance of Hole 84-567A. 3 records from Planktic foraminifera abundance of Hole 68-502C. 2 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 96 records from Schaalbach. 1178 records from Danielsberg (Mölltal, Kärnten). 849 records from CNAN/Scorpiones. 18 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 34 records from Pollen profile from site Kolbermoor2, Rosenheim, Oberbayern, Germany. 1306 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 478 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 16429 records from Collection Crustacea - ZMB. 186 records from Nannofossil abundance of Hole 82-558A. 23 records from Relative abundance of coccosphere-units of sediment core GIK23424-3. 19 records from Seeufer ehem. BUGA-Gelände. 16 records from Distribution of meiobenthos in sediment core M23_108 of the northeastern Atlantic (Table 1). 108776 records from UMMZ Mammal Collection. 142211 records from Entomological collections, UiB. 8070 records from SPC CoFish Fish Observations Marshall Islands 2007. 46528 records from Atlas of Danish Fishes. 184 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 8 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 216 records from BIRDRACE Diesmal sehen wir mehr. 10 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 54 records from Vögel. 68 records from Naturerlebnisraum Koppelsberg (Plön). 71 records from Revision of the funnel-web spider genus Novalena (Araneae: Agelenidae). 4121 records from Données Rhopalocères et Zygènes de la RNN Bruges - export réalisé pour le pré-Atlas régional en 2016. 34381 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 8914 records from Balsfjord Nature Reserves. 725 records from REPHY - Réseau d'Observation et de Surveillance du Phytoplancton et de l'Hydrologie dans les eaux littorales. 70 records from Données de Provence-Alpes-Côte d'Azur transmises par Pascal Peyrache.. 2 records from A new species of Pelecium Kirby (Coleoptera: Carabidae: Peleciini) from the Atlantic Forest biome, Brazil. 1764 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 3 records from Amphibiens filet/Comcom Chardon Lorrain. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 7 records from Further studies on south eastern Asian Luciolinae: 1. Sclerotia Ballantyne, a new genus of fireflies with back swimming larvae 2. Triangulara Pimpasalee, a new genus from Thailand (Coleoptera: Lampyridae). 6 records from A new species of Moenkhausia Eigenmann, 1903 (Characiformes: Characidae) from Amazon basin, Brazil. 500 records from Limited bat records from the Union & Forth and Clyde canals 2000-5. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 204688 records from Données de Mammifères collectées par le GMA et la LPO. 3 records from Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria). 19620 records from Likona Invertebrates. 159 records from Données d'observation des Marine Mammal Observers durant le levé sismique 3D SHELL en Guyane française en 2012 par Shell Exploration and Production France. 2 records from A cryptic new species of hummingbird of the Campylopterus largipennis complex (Aves: Trochilidae). 1 records from Parasitism of Hymenoepimecis manauara Pádua & Oliveira (Hymenoptera: Ichneumonidae: Pimplinae) on Leucauge henryi Mello-Leitão (Araneae: Tetragnathidae) in Brazilian Amazonian. 246210 records from Wicken Fen nature reserve species data held by The National Trust. 328501 records from USGS PWRC - Native Bee Inventory and Monitoring Lab (BIML). 334 records from (Fig. 5) Distribution of Chironomids of sediment core Lz1103 from Duck Lake. 53 records from Macquarie University Biodiversity and Conservation Student Observations. 11625 records from Actualización de la base de datos de la colección nacional de anfibios y reptiles (CNAR). 17 records from Two new species of Nazeris Fauvel in the Luoxiao Mountain Range, China (Coleoptera, Staphylinidae, Paederinae). 2 records from Kiwisaldula waiho and K. hurunui, two new species of Saldidae (Hemiptera: Heteroptera) from the South Island of New Zealand, with redescriptions of K. butleri (White) and K. laelaps (White). 6478 records from National System of Protected Areas in Poland - Animals. 6 records from First record of the genus Eucremastus Szépligeti, 1905 (Hymenoptera: Ichneumonidae: Cremastinae) from the Arabian Peninsula, with the description of three new species. 13366 records from CSIRO, Abundance and distribution of orange roughy in southeast Australian waters 1987-1979. 4276 records from Coleção Entomológica Padre Jesus Santiago Moure-Trichoptera (DZUP-Trichoptera). 84979 records from NINA Vanndata fisk. 19 records from Descriptions of three new species of the harvestmen genus Pseudogagrella (Opiliones: Sclerosomatidae: Gagrellinae) from Taiwan, supported by morphological and molecular evidence. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 11 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 42 records from Occurrence of mammalia relicts at site Kogelstein. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 72 records from Artenvielfalt im Umfeld der Burgwegschule. 218 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 32669 records from CNMA/Colección Nacional de mamíferos. 7638 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 5 records from Collection Hemiptera - SNSD. 3414 records from Species found in the NOMS estate 2005 - Present. 992 records from Inventario de los murciélagos de los parques nacionales Sierra de San Pedro Mártir y Constitución de 1857, Baja California, México. 36 records from (Table 10) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-686. 1920 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE255. 385 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE206. 690 records from Packer Collection /Madagascar. 1 records from Elasmopus sivaprakasami sp. nov., a new species of amphipod (Senticaudata, Maeridae) from Gujarat State, India. 13 records from Nannofossil abundance of Hole 39-353. 7 records from Nannofossil abundance of Hole 8-71. 3 records from Nannofossil abundance of Hole 6-57A. 19500 records from Natural History Museum Maastricht (NL) - Entomological Collection. 56 records from Coccoliths in sediment core GIK23065-3. 11 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 2322132 records from IMOS - Animal Tracking Facility - Acoustic Tracking - Quality Controlled Detections (2007 -2017). 2 records from Description of the male of Antodice quadrimaculata Martins & Galileo, 2003 (Coleoptera, Cerambycidae, Lamiinae), with new country record for the species. 24 records from City of Edinburgh Natural Heritage Service - Ranger Patrol Records. 187 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 3 records from Description of two new species in long-horned crane fly subgenus Tipula (Sivatipula) (Diptera: Tipulidae) from China. 115 records from Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010. 178581 records from LACM Entomology Collection. 24 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 40 records from Truchas Mexicanas. 5 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 3 records from Latheticomyia Wheeler (Diptera: Pseudopomyzidae) from Peru: new species, description of the male of L. longiterebra Hennig and a key to species. 3486 records from Marine Invertebrate from Argentina, Uruguay and Chile. 2156 records from Oceanexploration2002_vers4. 10 records from Description of a new species of Caridina (Crustacea: Decapoda: Atyidae) from two Micronesian islands (Guam and Babeldaob). 45 records from Caracterización Ecológica de la avifauna del Cerro Jánano. 3 records from Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 3 records from (Table 2) Eocene benthic foraminiferal community of DSDP Holes 95-613 and 11-108. 4 records from Nereididae (Annelida: Phyllodocida) of the Persian Gulf and Gulf of Oman, including description of two new species and 11 new records. 55 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Cragbank and Wolfehopelee SSSI. 24 records from The Giant Resin Bee, Megachile sculpturalis Smith: New Distributional Records for the Mid- and Gulf-south USA. 2142 records from Carabidae on grasslands 2008. 34 records from Ichneumonidae (Hymenoptera) species new to the fauna of Norway. 6797 records from Collection Herpetology SMF. 4 records from New earthworm species of Righiodrilus (Clitellata, Glossoscolecidae) from eastern Amazonia. 56 records from SuLaMa Amblyomma chabaudi occurence data. 12558 records from SPC CoFish Fish Observations Palau 2007. 186 records from Occurrence of mammalia relicts at site Pestera Livadita. 1568 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 2610 records from CNIN/Tipos Coleoptera. 141760 records from Naturalis Biodiversity Center (NL) - Aves. 7 records from A new species of the genus Phytoecia Dejean, 1835 (Coleoptera: Cerambycidae) from Greece. 20 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 386336 records from Estonian Nature Observations Database. 4522 records from Données oiseaux endémiques des Antilles sur le territoire de la Guadeloupe (ONCFS & PNG). 348 records from Australian Institute of Marine Science (AIMS) - Surveys of Octocoral communities, benthic cover and environmental factors on coral reefs of Milne Bay, Papua New Guinea (2002). 2 records from Revision of the genus Morphosphaera Baly (Coleoptera: Chrysomelidae: Galerucinae). 8 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 2 records from (Table S2) Coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 194 records from Database_diptera. 93 records from Données naturalistes de Pierre NOEL (M2MNHN). 70 records from A taxonomic monograph of the genus Dodomeira Bellò & Baviera, a new genus of Peritelini from Sicily (Coleoptera: Curculionidae: Entiminae). 18 records from Lost and found: the Plecoptera types of Blanchard and Mabille, with further contributions to the stoneflies of Chile. 2 records from Range table from benthic foraminifers in ODP Hole 149-897D. 4 records from Range table from planktonic foraminifers in ODP Hole 167-1012A. 150 records from Occurrence of mammalia relicts at site Sveduv stul. 118 records from NSG Nollig. 1 records from Colección de microorganismos del CINVESTAV-IPN Fase I, Base de datos, Parte Vista Usuarios Internos. 1482 records from Benthic communities and environmental parameters in Amvrakikos Wetlands: Mazoma, Tsopeli,Tsoukalio, Rodia and Logarou lagoons (September 2010 – July 2011). 737 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 122 records from BIRDRACE Bergische Ornis. 60 records from Meiofauna abundance in sediment core 13368-019. 39 records from Meiofauna abundance in sediment core 13077-021. 27 records from Range table from ostracoda in ODP Hole 160-967A. 5 records from Nannofossil abundance of Hole 29-278A. 3 records from Nannofossil abundance of Hole 3-18. 3 records from Liether Park (LMS), 6g. 29 records from Meiobenthos investigations in the Black Sea during Poseidon cruise POS317/3. 2939 records from Données naturalistes de Pierre NOEL (pnoel). 28 records from Microzooplankton abundance and biomass at station TT045_21-25. 345 records from BIRDRACE Guckers Offenbach. 36 records from Schulgelände Paul-Gerhardt-Schule. 268 records from Thistle Heads and Ermerged Insects. 2 records from A new species and a new record of the spider genus Nesticus (Araneae, Nesticidae) from southern Brazil. 8 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 18 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 133370 records from CAS Invertebrate Zoology (IZ). 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 128 records from Análisis ecológico de la ornitofauna de la ciénaga La Honda, Tanguí. 618 records from DBRC Austropotamobius pallipes records 1960 - 2015. 8427 records from IZIKO: Marine Invertebrate Collection (1900-2011). 26 records from The Panjange nigrifrons group in Borneo (Araneae: Pholcidae): high diversity in Sarawak, apparent absence in Sabah. 45351 records from Fiocruz/COLFLEB - Coleção de Flebotomíneos. 353106 records from Dry Tortugas Reef Visual Census 2014. 3255 records from Captura de datos de la Colección de Curculionoidea (Insecta: Coleoptera) de la Universidad Autónoma de Querétaro. 1 records from Synthèse de la répartition des populations de cerf élaphe en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2 records from Taxonomy of the genus Pristidia Deeleman-Reinhold, 2001 (Araneae: Clubionidae) in China. 65196 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 20212 records from CSIRO, fish surveys by the Courageous, 1978-1979. 5 records from Tracking saltwater crocodiles on the Wenlock River, Cape York, Queensland, Australia 2012_13. 1203 records from Scientific Results of the New Zealand Government Trawling Expedition, 1907. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 411926 records from New Zealand research tagging database. 66986 records from Dreal Corse - Base Ogreva. 26040 records from Données de l'atlas des Mammifères sauvages de Midi-Pyrénées (données agrégées à la maille de 10km). 559 records from Crustacea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 14741 records from Trekvis - Migratory fishes in the river Scheldt. 2 records from Synthèse de la répartition des populations de cerf élaphe en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 195474 records from MSB Fish Collection (Arctos). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 376 records from Situación actual del búho manchado mexicano (Strix occidentalis lucida) y de los Strigiformes de la Reserva de la Biósfera La Michilía. 3 records from A revision of the New Zealand weevil genus Irenimus Pascoe, 1876 (Coleoptera: Curculionidae: Entiminae). 46 records from (Table 3) Distribution of benthic foraminifera in Neogene sediments of DSDP Site 90-590 in the southwest Pacific. 341 records from Données naturalistes de Laurent CHAPELLIERE. 205 records from Occurrence of mammalia relicts at site L´Abri Duruthy. 2312 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 77112 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 10458 records from European Moth Nights. 5440 records from Fish Collection of Yokosuka City Museum. 2093 records from Elasmobranquios del Golfo de Tehuantepec, litoral chiapaneco. 10 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 46 records from (Table 7) Distribution of Maestrichtian to late Campanian nannofossils in ODP Hole 108-661A. 62 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific. 2048 records from Données naturalistes d'Emmanuel SECHET. 54 records from Nannofossil abundance of Hole 55-433. 3253 records from Hemiptera: Auchenorrhyncha: Records for Kent. 7 records from Nannofossil abundance of Hole 6-50A. 3 records from Nannofossil abundance of Hole 1-4. 13 records from Ostracoda abundance of Hole 42-375. 3 records from Atlas de la flore de la forêt du Madrillet. 6329 records from Estudios bióticos: Plantas, anfibios, mamíferos, aves y edafofauna epígea (coleópteros y arácnidos), en el complejo de páramo Los Nevados. 256 records from BIRDRACE Oostfreesland Bird-Lopers. 20 records from schlittschuhweiher. 6 records from Oschenberg, NO von Bayreuth-Laineck. 8 records from Living and fossil Steginoporellidae (Bryozoa: Cheilostomata) from New Zealand. 167384 records from ummz_fish. 31 records from Great Eastern Ranges - Southern Highlands. 144 records from Données naturalistes de DELANNOYE Régis. 114 records from On the Nazeris fauna of Zhejiang, China (Coleoptera, Staphylinidae, Paederinae). 145 records from UCM Vertebrate Observations Collection (Arctos). 258 records from Cnidarios del proyecto Macrofauna Corpoguajira. 3 records from New species of Poecilocloeus Bruner, 1910 (Orthoptera: Acrididae: Proctolabinae) from Paraná State, Brazil. 3 records from Recharacterization of Rhinophis dorsimaculatus Deraniyagala, 1941 (Serpentes: Uropeltidae), including description of new material. 62 records from Occurrence of mammalia relicts at site le Roc de Marcamps. 27 records from Occurrence of mammalia relicts at site Meiendorf. 34 records from Schulgarten Paul-Schneider-Schule, Münster. 22 records from Hemmerder Schelk (Unna). 34331 records from UCM Amphibian and Reptile Collection (Arctos). 11 records from The genus Anarsia Meyrick (Lepidoptera, Gelechiidae) in Laos, with description of a new species and ten new records of the genus. 146 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 3 records from Benthic macrofauna abundance of sediment core 12930-022. 36 records from Meiofauna abundance in sediment core 12930-036. 194 records from Programme delphinidés 2007-2010 à Mayotte. 8 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 2 records from Nannofossil abundance of Hole 25-249. 3 records from Nannofossil abundance of Hole 3-13. 45542 records from Mollusca specimens of Toyama Science Museum. 158 records from BIRDRACE Blinde Hühner. 4 records from VFD-RP: Eifel: Orchideenweide Ankly. 577 records from Schulzentrum "Parc Hosingen". 26 records from Schulhof Sandhofenschule (Mannheim). 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 20 records from Revision of the Agrilus quadripunctatus species-group (Coleoptera: Buprestidae: Agrilini) with description of four new species. 2027 records from DREAL Auvergne - Avifaune - 2015. 3 records from A new species of the endemic South African spider genus Austrachelas (Araneae: Gallieniellidae) and first description of the male of A. bergi. 1 records from Synthèse de la Répartition des populations de mouflon corse en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1324 records from Snipe survey of key sites in Britain in 2006. 2808 records from Nymphalidae Ithomiinae. 83 records from Seaflower ll: Cayo Serrana- Colección biológica universidad CES. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 447 records from DragonflyPix.com Australian observations. 11418 records from Coleoptera of Piska Forest. 128008 records from Environment Agency England and Wales (2007) freshwater invertebrate species (single species families). 1 records from Diversity of shrews in Ethiopia, with the description of two new species of Crocidura (Mammalia: Lipotyphla: Soricidae). 6 records from Three new species of Oxysarcodexia Townsend (Diptera: Sarcophagidae) from the Colombian Andes. 408 records from Censo del Zarapito Trinador (Numenius phaeopus) y Otras Aves Acuáticas en el Parque Nacional Natural Sanquianga. 2002 records from LACM Invertebrate Paleontology. 141 records from (Table T3) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1138A. 39 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1209C. 68 records from Freshwater Site Visits and Ad-hoc Sightings. 10219 records from Data from Defra Family Organisations supplied to Staffordshire Ecological Record. 25174 records from Diptera collection, Natural History Museum, University of Oslo. 40021 records from SEAPOP - Last observation per locality in winter season. 1364 records from Long-lasting effects of logging on beetles in hollow oaks. 1 records from Dinoflagellate cysts of ODP Hole 189-1171D. 19 records from Foraminifera abundance of Hole 64-477. 1 records from A new Eocyzicus (Branchiopoda: Spinicaudata) from Taiwan, with a review of the genus. 188 records from Birdrace-Filz_Fledermäuse-Münster. 547 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 5214 records from Swiss Psyllid (Hemiptera) Collections - Basel. 11 records from (Table 5) Composition of stomach boluses of flounders in the West Bay of the Furugelm Island (Sea of Japan) in summer 1991. 27 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 8834 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 7 records from (Table 1) Numerical abundance counts of planktonic foraminifers and other biogenic constituents for ODP Hole 114-698A. 736 records from Ostracoda in sediment core BP00-07/05. 35 records from Meiofauna abundance in sediment core 12930-018. 258 records from Petrography, carbonate mineralogy and texture of carbonate rocks of Meteor and Josephine Seamounts, eastern North Atlantic (Table 5). 25 records from Ostracoda abundance of Hole 32-306. 391 records from (Table 7) Ostracod assemblages of sediment core 9408. 31 records from Naturpark Kottenforst-Ville 18.6.09. 1288 records from DREAL_PACA_-_N2000_-_Conseil_Général_83_2017_12_18. 112 records from Brander Wald (Stolberg). 154 records from Feriendorf des Kreises Gedern (Ober-Seemen). 15436 records from Census of the animals of Benin. 4 records from A new species and new record of the genus Nannastacus (Crustacea: Cumacea: Nannastacidae) from Korea. 2696 records from Caracterización y monitoreo de la condición arrecifal en cinco áreas naturales protegidas y un área de influencia de Quintana Roo, México: Primera etapa. 9 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 5 records from First records of Pseudodoros nigricollis Becker (Diptera: Syrphidae) from Cyprus. 119 records from SEWBReC Marine and other Aquatic Invertebrates (South East Wales). 16 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 17 records from New species and new records of Calycomyza Hendel (Diptera: Agromyzidae) in Brazil. 1 records from A new species of Anheteromeyenia (Porifera, Demospongiae) with an emended diagnosis of the genus. 3498 records from Inventario de corales pétreos, asteroideos, equinoideos y peces óseos de arrecifes de la costa de Jalisco, Colima y Michoacán. 4 records from A new species of small and highly abbreviated caecilian (Gymnophiona: Indotyphlidae) from the Seychelles island of Praslin, and a recharacterization of Hypogeophis brevis Boulenger, 1911. 2 records from A review of the arboreal Afrotropical ant genus Axinidris.. 30 records from World review of the genus Strongylophthalmyia Heller (Diptera: Strongylophthalmyiidae). Part I: Introduction, morphology, species groups, and review of the Strongylophthalmyia punctata subgroup. 824 records from Diversidad del ictioplancton en las lagunas Madre y Almagre, Tamaulipas, y laguna de Tampamachoco, Veracruz. 32 records from Taxonomic and morphological revision of butterfly rays of the Gymnura micrura (Bloch & Schneider 1801) species complex, with the description of two new species (Myliobatiformes: Gymnuridae). 685 records from Ostracode relative abundances and geochemistry in surface sediments from Lake Ohrid. 1373 records from Australian Institute of Marine Science (AIMS) - CReefs Ningaloo Reef Biodiversity Expedition, Australia (2008 - 2010). 7 records from Chaetognatha collection of National Museum of Nature and Science. 12 records from A new species of Gynacantha Rambur, 1842 from Cat Tien National Park, Vietnam (Odonata: Aeshnidae). 1 records from Isoperla vjosae sp. n., a new species of the Isoperla tripartita group from Albania (Plecoptera: Perlodidae). 18 records from Negros Cave Frog Observation. 17 records from Lund Botanical Museum (LD). 58 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 9 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 420 records from Black grouse lek surveys in the Scottish Borders, 2010-2011. 368 records from Biological Recording in Scotland - Bumblebee Survey. 1211 records from Naturalis Biodiversity Center (NL) - Tunicata. 2536 records from Makira. 92 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 26 records from (Appendix A1) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1209B in the central Pacific. 1 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 42 records from CERMES Barbados Lionfish Sightings 2012. 97 records from Planktic foraminifera abundance of Hole 18-173. 508 records from Non Native Species Across Wales (1989 to 2012). 130 records from Occurrence of mammalia relicts at site Remetehegy. 2 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200590. 270 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 44 records from Küste Wismar-Wendorf bis Hoben. 3721 records from Caddisfly (Trichoptera) records from Britain and Ireland, via iRecord. 2 records from A new species of the genus Clistoabdominalis Skevington (Diptera: Pipunculidae) from Iran, with a key to the Western Palaearctic species of the Clistoabdominalis ruralis group. 2161 records from SMAEMV_2017_12_18. 10 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 48 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 6 records from Phthinia Winnertz (Diptera: Mycetophilidae): new species and records from the Neotropical and Oriental regions. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 31894 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 1 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 123284 records from Sustainable Rivers Audit. 38033 records from Tamborine Mountain Weekly Bird Observations. 3757 records from Fish collection, Natural History Museum, University of Oslo. 79 records from Collection des données de biodiversité marine de Polynésie française - IRD Nouvelle-Calédonie. 1 records from A review of North American Elonus species, with description of E. gruberi n. sp. (Coleoptera: Tenebrionoidea: Aderidae). 114 records from Jeu de données convention golf de Vidauban 2016-2022. 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 10 records from A new species of Phosocephala Townsend, 1908 (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica. 4126 records from IICT Colecção Zoológica. 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 1671 records from Inventaire amphibiens reptiles dans la partie béarnaise du Parc National des Pyrénées. 12940 records from Hymenoptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 7 records from Four new species of Cymadusa Savigny, 1816 (Amphipoda: Ampithoidae) and new records of C. filosa Savigny, 1816 from Brazilian coast. 4908 records from Amphibian and reptile data for Dumfries and Galloway.. 3312 records from USGS SESC - Everglades - Herpetofauna - 2000-2002. 24 records from First record of the genus Ficobracon (Hymenoptera: Braconidae) from India, with description of new species. 12 records from UWS Flanders Moss Meiofauna Records 2015. 11176 records from Snow Petrel nest census, Mawson region 2004/05. 674 records from FSUCML Zoological Collections. 4 records from Planktic foraminifera abundance of Hole 67-500. 3246 records from Censo de primates de la Fundación Entropika. 16 records from Planktic foraminifera abundance of Hole 14-141. 12 records from Occurrence of mammalia relicts at site Kobbelgard/Loc4. 40 records from Planktic foraminifera abundance of Hole 4-30. 17 records from A checklist of the praying mantises of Peru: new records, one new genus (Piscomantis gen. n.) and biogeographic remarks (Insecta, Mantodea). 204 records from Halberg bei Neumorschen. 592 records from Gewann Krampf (Heilbronn). 4 records from Analyses of the recent components of sediment core PS1013-1. 1694 records from The Ecology of the Inshore Marine Zooplankton of the Chukchi Sea near Point Barrow, Alaska. 2674302 records from Point Reyes Bird Observatory - Point Counts. 61534 records from SDNHM Herpetology Collection. 60184 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Bag Seine. 4 records from Collection Herpetologie - SNSD. 134 records from (Table 7) Distribution of early to middle Eocene calcareous nannofossils in ODP Hole 149-900A. 228 records from Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West. 36 records from Palynology of profile Füramoos III. 25 records from Pollen profile ADR309. 134 records from Nannofossil abundance of Hole 94-610A. 13 records from Ostracoda abundance of Hole 44-390. 93 records from Nannofossil abundance of Hole 5-34. 4 records from Phytoplankton abundance at station CD46_1305C#2. 62 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211630-9. 66 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 51 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 48 records from Langes Tannen(LMS), Klasse 5d. 4 records from Hildener Heide - Spörkelnbruch (Haan). 146 records from The Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 66 records from Spiders of French Guiana. 22 records from Review of the Eriococcidae (Hemiptera: Coccomorpha) infesting Fabaceae in Argentina, with descriptions of three new species of Acanthococcus Signoret. 7581 records from Invertebrate collection of University of Oulu Zoological Museum. 120 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 739 records from Leicestershire and Rutland Invasive Non-Native Species. 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 3565 records from UMNH Reptiles and Amphibians Collection (Arctos). 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1986 records from ROC RSPB Farmland Species Survey Dataset. 1418 records from Vertebrados terrestres de San Juan de Camarones, Durango. 116 records from Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 6 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 569 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 23141 records from Computarización de abejas de la colección entomológica de la Frontera Sur. 4193 records from Leicestershire and Rutland Aculeate Records. 9780 records from SEWBReC Molluscs (South East Wales). 5625 records from RAVON (NL) - Network Ecological Monitoring Reptiles. 1 records from new endemic Synagapetus species (Trichoptera: Glossosomatidae) from Madeira Island (Portugal). 2 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 4919 records from Abundances indices and biological traits of juvenile salmon sampled in the Nivelle river (France). 23 records from Diversity and distribution patterns of Calcareous sponges (subclass Calcinea) from Martinique. 1448 records from LPO_2017_12_18. 2 records from Revision of the Oriental species of Calleida Latreille (sensu lato). Part 1: Introduction, groups of species, and species of six species groups (Coleoptera: Carabidae: Lebiini). 54 records from Análisis ecológico de la mastofauna en la parte alta del Rio Güangui. 557 records from Corn bunting breeding distribution in Scotland. 2 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 107 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 5576 records from Parc_Naturel_Régional_du_Queyras_2017_12_18. 21 records from New species of Chimaera (Chondrichthyes: Holocephali: Chimaeriformes: Chimaeridae) from the Southwestern Indian Ocean. 4328 records from Otter Survey of Ireland 1982. 969 records from Coleoptera of Tuchola Forest and Tuchola Forest National Park. 342 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 2394746 records from Hatikka Observation Database. 119 records from Kinorhyncha. 28 records from New dendrochirotid sea cucumbers from northern Australia (Echinodermata: Holothuroidea: Dendrochirotida). 5324 records from Macrobenthos and Meiobenthos Tuktoyaktuk Harbor and Mason Bay 1985-1988 NOGAP. 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 40 records from Naturalis Biodiversity Center (NL) - Cainozoic Mollusca. 2431244 records from Finnish Winter Bird Census. 31 records from Abundance of benthos infauna at station GIK23060-1. 188 records from Collection Cnidaria fossil SMF. 6 records from Two new species of Cercyon (Clinocercyon) from Russian Far East (Coleoptera: Hydrophilidae). 2 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 7 records from Planktic foraminifera abundance of Hole 71-513A. 2 records from Dinocyst assemblages of site HM52-43. 36 records from Schulumgebung Grüterschule, Rheine. 132 records from Promberg1. 2 records from Three new species of cockroach genus Hemithyrsocera Saussure, 1893 (Blattodea: Ectobiidae: Blattellinae) with redescriptions of two known species from China. 48 records from Tettigettalna josei (Boulard, 1982) (Hemiptera: Cicadoidea): first record in Spain, with notes on the distribution, genetic variation and behaviour of the species. 17 records from CNAN/Tipos Arachnida. 16459 records from FHSM Herps Collection. 7900 records from NBM birds. 10699 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 15 records from Pollen record of peat sequence Barbarina Tumsa. 54818 records from Occurrence d'ongulés et Lagomorphes de Bourgogne synthétisées par la Société d'histoire naturelle et des amis du muséum d'Autun (SHNA). 13 records from Echiura - SMF. 8 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 20 records from Nannofossil abundance of Hole 17-167. 37 records from Abundance of coccosphere-units of sediment core GIK23411-5. 2 records from Abundance of radiolaria at station UT99-21-2. 148 records from Faunal assemblage of ODP Hole 101-633A (Table 2). 1 records from Cataglyphis tartessica sp. n., a new ant species (Hymenoptera: Formicidae) in southwestern Spain. 98 records from Relative abundances of dinoflagellate cysts in several IODP and DSDP holes. 3348 records from Cnidarios, poliquetos, crustáceos (decápodos) y quetognatos pelágicos del Golfo de California. 10149 records from Bumblebees, cuckoobees and butterflies in southern Poland. 1 records from Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867). 31 records from Benthic macrofauna abundance of sediment core 13200-020. 26 records from Benthic macrofauna abundance of sediment core 13077-063. 21 records from (Table 14) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-592. 30 records from Nannofossil abundance of Hole 24-232. 242 records from Nannofossil abundance of Hole 15-149. 1 records from Données naturalistes de Marcel CRUVEILLIER. 1 records from A new species and notes on unusual natural history of Cladochaeta Coquillett, 1900 (Diptera: Drosophilidae). 572 records from CNAC/Coleccion Nacional de Acaros. 96 records from Invertebrate collections. 202 records from Centre d'Estudis Avançats de Blanes. Limnological Observatory of the Pyrenees - Rotíferos y crustáceos en lagos pirenaicos. 164 records from (Enclosure 1, Fig. 1) Complete pollen spectra of the samples represented by the composite pollen diagram from site Samerberg. 135 records from (Table 11) Distribution of planktonic foraminifers in ODP Hole 112-688E. 18 records from (Appendix A) Abundance of benthic foraminifera in sediment core GIK17940-2. 114 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/567-1. 106 records from Birds (GNHM-BI). 21 records from Benthic macrofauna abundance of sediment core 13200-025. 9 records from Nannofossil abundance of Hole 38-349. 1405 records from Computarización de la colección de moluscos holoplanctónicos del Golfo de California y Golfo de Tehuantepec. 50 records from Nannofossil abundance of Hole 78-542A. 114826 records from Atlas of Danish Mammals. 14718 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 3 records from Benthic foraminifera abundance of ODP Site 184-1143. 14 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 156 records from Birdrace-Die_Laufenten-Braunschweig. 56 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 2 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 7641 records from Distribution of Butterflies in Greater Manchester. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 44226 records from Global compendium of Aedes albopictus occurrence. 720 records from Saproxylic beetles of the Po plain woodlands, Italy. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 733 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 10 records from A new genus of ground and litter-dwelling pholcine spiders from Sarawak (Araneae, Pholcidae). 296510 records from Dry Tortugas Reef Visual Census 2008. 177148 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 1628 records from Données naturalistes de Quentin ROME. 3027 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la palangre. 2 records from A new Caryophyllaceae-feeding species of Macrosiphum (Hemiptera: Aphididae) in Republic of Georgia, and a redescription of Macrosiphum hartigi Hille Ris Lambers. 5991 records from Peces asociados a los arrecifes coralinos del norte de Veracruz. 2270 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 31787 records from Observatoire de la Biodiversité des Jardins (OBJ). 699 records from Censo abundancia de aves en los Parques Nacionales Naturales de Bahía Malaga, Portete y Old Providence. 945 records from Inventario de Aves Mámbita. 143984 records from Colección de Entomología del Instituto Alexander von Humboldt. 11 records from Two new species of Suberitida (Porifera, Heteroscleromorpha) from the Bering Sea. 15 records from Blattaria Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 24219 records from Données naturalistes de Pierre HUGUENY. 215 records from VIP_data_topsoil_soilfoodweb_spring_2008. 426 records from Données du Centre de la mer de Biarritz. 24293 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Gill Net. 4303 records from Actualización y sistematización de la colección de referencia de invertebrados de la Estación Mazatlán-UNAM. 2 records from Données naturalistes de DURON Cyril. 129 records from Abundance of benthos infauna at station GIK23006-3. 30 records from Foraminifera abundance of Hole 57-440B. 164 records from Occurrence of mammalia relicts at site Rusenschloß. 400 records from Occurrence of mammalia relicts at site Pod hradem. 2885 records from Données naturalistes de Cyrille DELIRY. 2 records from Analyses of the recent components in the sand fraction of sediment core PS1222-1. 1019055 records from VerteCAT: Banco de datos de vertebrados de Cataluña. 9740 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 552 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 366 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 1383 records from Distribución e inventario de algunas especies bentónicas (hexacorales, octocorales, esponjas, y especies misceláneas) en arrecifes del Caribe mexicano. 5580 records from Filogenia del género Conopsis Günther (Serpentes: Colubridae). 71 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832B. 109 records from (Table 6) Distribution of ostracode species in surface sediments of the western Laptev Sea. 194 records from (Table 4b) Calcareous nannofossil distribution on ODP Hole 117-721B. 3 records from Ostracoda abundance of Hole 13-129A. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 20 records from Sandloch - Höhle. 282 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Chelicerata (ZUFMS-CHE). 127 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/356-1. 82 records from Microzooplankton abundance measured on water bottle samples at station PS58/090-4. 24 records from On the taxonomy of the genera Planovalvata Dubatolov & Kishida, Stigmatophora Staudinger and Pseudomiltochrista Dubatolov & Bucsek, with description of one new species (Lepidoptera, Erebidae, Arctiinae, Lithosiini). 1 records from Cyrtodactylus tahuna sp. nov., a new bent-toed gecko (Reptilia: Squamata: Gekkonidae) from Sangihe Island, North Sulawesi, Indonesia. 44 records from Königsdorfer Wald. 537 records from BIRDRACE Kosmos-Racer. 17 records from Australian species of Ommatius Wiedemann (Diptera: Asilidae) with an anepimeral bristle. 4 records from Tanypus urszulae, a new Tanypodinae (Diptera: Chironomidae) from the Neotropical Region. 54 records from Mühlenbach bei Buxtehude. 32 records from Regenrückhaltebecken Bad Bevensen. 36 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 25 records from Base de données en ligne d'observations naturalistes de mammifères marins. www.faune-guyane.fr. GEPOG & LPO. 1 records from Additional three new species of Anarsia Meyrick (Lepidoptera, Gelechiidae) from Cambodia and Vietnam. 891 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 8 records from New species of Pseudosinella Schäffer, 1897 (Collembola, Entomobryidae) from Hungary. 1151 records from arim. 14881 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 3 records from ZUEC-NMA - Coleção de Nematoda do Museu de Zoologia da UNICAMP. 6992 records from Stone-curlew Annual Surveys. 1 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 1401 records from Données de l'atlas des Mammifères sauvages de Midi-Pyrénées (données agrégées à la zone hydrographique de la BDcarthage). 1 records from An annotated checklist of the Chilopoda and Diplopoda (Myriapoda) of the Abrau Peninsula, northwestern Caucasus, Russia. 106 records from Michael Barkla's Observations. 2 records from Potamonautes nheenae, a new species of freshwater crab from Gabon, Central Africa, with a description of the first known male of Erimetopus brazzae (A. Milne-Edwards, 1886) from the Democratic Republic of the Congo, Central Africa (Brachyura: Potamoidea: Potamonautidae). 1682 records from Ghent University - Zoology Museum - Vertebrate collection. 42 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 4140 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from New species of Leleja (Orthoptera: Gryllinae; Gryllini) with first female description for the genus. 2 records from SWECO. 152 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 40 records from Microzooplankton abundance and biomass at station TT045_27-4. 8 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 204 records from BIRDRACE Buteo1DO. 2367 records from Données naturalistes d'Alice MICHAUD. 4 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 177 records from DBRC Trichoptera 1974 - 2015. 2 records from REDESCRIPTION OF TETRAMORIUM ATLANTE CAGNIANT, 1970, NEW STATUS (HYMENOPTERA: FORMICIDAE: MYRMICINAE). 99 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 7 records from A new species of Crenitulus Winters, 1926 (Coleoptera: Hydrophilidae: Chaetarthrinae: Anacaenini) from northern South America. 2697 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 12 records from Revision of the Recent species of Exechonella Canu & Bassler in Duvergier, 1924 and Actisecos Canu & Bassler, 1927 (Bryozoa, Cheilostomata): systematics, biogeography and evolutionary trends in skeletal morphology. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 1382250 records from Liste des espèces de la faune sauvage (Amphibiens, Mammifères hors Chiroptères, Oiseaux, Orthoptères, Reptiles & Rhopalocères) observées selon le maillage communal français de la base de données naturalistes Faune-France .. 896666 records from SEFSC CAGES Alabama Fish Length Data with CPUE. 7513 records from List of animalia, fungi and plant species recorded through naturalist observations and research activities in Benin. Data mobilized in the framework of a JRS Biodiversity Foundation project of Benin. 4363 records from Données de Cerambycidae et de Scarabaeoidea du Limousin. 87 records from UWIZM Arachnids. 230 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 2215 records from Base de datos de la Colección zoológica del Instituto de Investigación de zonas desérticas de la Universidad Autónoma de San Luis Potosí (BDCZIID-UASLP). 96 records from Wildlife Observations Bardon Hill 31.5.09. 568 records from Invertebrados y aves playeras de la Laguna Madre de Tamaulipas, México. 647 records from ZFMK Diptera collection. 77210 records from Oiseaux nicheurs de France métropolitaine 1985-1989 - nidification certaine. 4 records from A spectacular new species of seadragon (Syngnathidae). 172 records from UWIZM Cnidarians. 1 records from Some Hydroids (Cnidaria, Hydrozoa) from the Great Australian Bight in the collection of the South Australian Museum. 67422 records from RNF - CEN Nord-Pas-de-Calais. 1842 records from Inventaires malacologiques en Pays de Savoie. 521 records from RV Investigator Voyage IN2017_T01 Seabird Observations, Australia (2017). 106 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 29958 records from UCT: Southern African Reptile Conservation Assessment (1910-2009). 13 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 51 records from Herbario ABH (Universidad de Alicante). 364 records from Table 3. Macrofossils of invertebrate animals. 8481 records from Insect Collection of Saitama Museum of Natural History. 5907 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 316 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 112-682A. 88 records from Distribution of late Neogene age calcareous nannofossils in ODP Hole 111-677A (Table 2). 396 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 46825 records from Saltabel - Orthoptera in Belgium. 4 records from A new species of leucosiid crab (Decapoda: Brachyura: Leucosiidae) from the Arabian Gulf. 5 records from Nannofossil abundance of Hole 51-417B. 13979 records from MfN - Fossil vertebrates IV. 14 records from (Appendix 2-4) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 31-292 in the western Pacific Ocean. 170 records from Epi-endofauna abundance in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 1 records from A new species of the genus Barsura Volynkin, Dubatolov & Kishida from China (Lepidoptera, Erebidae, Arctiinae). 10 records from Trap data GBZ4, 696 m. 52 records from Rechts des Inn Höhe Hofau Rosenheim. 212 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 544 records from BIRDRACE Niederlausitz-Team. 5 records from A review of the Macropes Motschulsky (Hemiptera: Lygaeoidea: Blissidae) from China, with descriptions of three new species. 30 records from Goethe-Hauptschule/Projekt I-10. 27498 records from Données de répartition de l’association FLAVIA A.D.E. acquises avec un financement public.. 683 records from Queensland Herbarium Records. 3 records from A new species of the spider genus Plator (Trochanteriidae) from south China. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 12 records from Revision of world Austroterobiinae and Parasaphodinae (Hymenoptera: Chalcidoidea: Pteromalidae), parasitoids of giant scales (Hemiptera: Coccoidea: Monophlebidae). 535 records from Images of Flora and Fauna of 290 Leppitt Rd, Upper Beaconsfield. 2 records from Description of two new Capnia species (Plecoptera: Capniidae) from the Hengduan Mountains of southwestern China. 10 records from Caracterizacion Ecologica de la Fauna de Anfibios Presentes en la Zona de Influencia de la Parte Alta del Rio Guangui. 7462 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 6436 records from Isle of Man historical wildlife records 1995 to 1999. 3027 records from Murray-Darling Basin fish monitoring survey. 5944 records from Lothian Wildlife Information Centre Secret Garden Survey. 166 records from Revision and cladistic analysis of the Southeast Asian leaf-dwelling spider genus Calapnita Simon (Araneae, Pholcidae). 67 records from Bioimages. 20 records from New species of Dichogaster Beddard, 1888 (Clitellata: Benhamiidae) with additional records of earthworms from Guadeloupe (French West Indies). 3 records from A new Costa Rican species of Leptanilloides (Hymenoptera: Formicidae: doryline section: Leptanilloidinae).. 52 records from Six new species and new records of the spider genus Chrosiothes from Brazil with the description of the female of Chrosiothes venturosus Marques & Buckup, 1997 (Araneae, Theridiidae, Spintharinae). 11 records from Clubionidae from Laos and Thailand (Arachnida: Araneae). 21 records from Arachnid specimens of Ryukyu University Museum (Fujukan). 4955 records from Dipterists Forum - Field Week 1999 (North West England). 13304 records from CWS: Waterbird colony database (Atlantic region). 2416 records from Zooplankton Bering Strait Tiglax 1991. 12 records from Five new species of Spartaeus Thorell, 1891 from China (Araneae: Salticidae). 3 records from Notoraja martinezi sp. nov., a new species of deepwater skate and the first record of the genus Notoraja Ishiyama, 1958 (Rajiformes: Arhynchobatidae) from the eastern Pacific Ocean. 3 records from Nocturnal Velvet Ants (Hymenoptera: Mutillidae) of Joshua Tree National Park, Riverside County, California with the description of three new species. 155 records from Catalogue of the type specimens of Pogonophora (Annelida; seu Polychaeta: Siboglinidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 21032 records from TPWD HARC Texas Coastal Fisheries Lower Laguna Madre Gill Net. 2 records from Revision of the ant genus Anillomyrma Emery, 1913 (Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 2 records from Field Museum of Natural History (Botany) Pteridophyte Collection. 1 records from A new Setacheres (Copepoda, Siphonostomatoida, Asterocheridae) associated with Ircinia felix (Duchassaing & Michelotti) (Porifera) from Brazil. 14 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 72015 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe). 25 records from Planktic foraminifera abundance of Hole 73-522. 50 records from Occurrence of mammalia relicts at site Buchenloch. 156 records from Occurrence of mammalia relicts at site Goyet Cave 3. 12 records from Occurrence of mammalia relicts at site Seest. 162 records from Hintere Halde. 346 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 94 records from Hüttenseepark (Meißendorf). 170 records from Am Moosangerweg. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 12 records from (Appendix B) Analyses of sulfides of ODP Leg 121 basalts. 48 records from Pollen profile Märchenwald B, Harz, Germany. 2819 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE255. 348 records from Antarctic pycnogonids. 25 records from Nannofossil abundance of Hole 74-526C. 3 records from Nannofossil abundance of Hole 3-14. 2969 records from Cladocera distribution updates 2014. 2104 records from Benthos counted on dredged samples during Valdivia cruise VA44. 34211 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 2 records from Données naturalistes d'Emilie WEBER. 56 records from Kabelskebach (Kabelsketal, Saalkreis). 68 records from Chinches patinadoras (Hemiptera: Heteroptera: Gerridae) de Colombia: taxonomía, distribución y datos biológicos. 470 records from The Sea Ice Fauna of Frobisher Bay, Arctic Canada 1981 and 1982. 2 records from A new canopy-dwelling species of Dendrelaphis (Serpentes: Colubridae) from Sinharaja, World Heritage Site, Sri Lanka. 2 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 1 records from Synthèse de la Répartition des populations de chamois en 1994 (réseau Ongulés sauvages ONCFS-FNC-FDC). 539 records from Données naturalistes d'Anthony DORE. 1 records from Allan Herbarium (CHR). 38618 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 510 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 18446 records from Arctic Marine Fish Museum Specimens. 1946 records from Freshwater Fishes of Bulgaria. 3 records from Two new species of Laonice (Norgensia) (Spionidae, Polychaeta) from subtropical Atlantic and subequatorial Pacific coasts of North America. 4096 records from Barrow Island Ants. 1 records from Tweed Council Koala Count. 13904 records from Bird collection NTNU University Museum. 66 records from Occurrence of mammalia relicts at site Stematia. 116 records from Phytoplankton abundance in surface water during cruise Alkor 237-1. 610 records from Riedensee. 326 records from (Appendix B2) Distribution of planktic foraminifera in ODP Hole 181-1125A east of New Zealand. 1 records from Opisa takafuminakanoi, a new species of Opisidae from Hokkaido, Japan (Crustacea: Amphipoda). 6 records from Analyses of the recent components of sediment core PS1016-1. 251736 records from Mosquito Occurrence Dataset. 1 records from A new species of Sweltsa (Plecoptera: Chloroperlidae) from Sichuan Province of southwestern China. 196 records from Inventaire malacologique du site Natura 2000 FR9301547 du Grand Coyer (2007, ONF/MNHN). 36 records from (Table 3) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897C. 84 records from (Table 2) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-698A. 210 records from Noble Chafer: Pre-BAP records prior to 1998. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 1259 records from Computarización sistemática de los bivalvos y gasterópodos de la sección húmeda de la Colección Malacológica Dr Antonio García-Cubas. 4845 records from Inventaire des Mollusques Sphaeriidae de France. 72 records from Nannofossil abundance of Hole 49-408. 130 records from Schieferbrüche. 284 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 15964 records from Lepidoptera Records up to April 2010. 262 records from BIRDRACE Brut. 138 records from BIRDRACE Pfeifenten. 16 records from Eichendorf Weiher Schwalbach a.Ts.. 76 records from Roter Berg Werdau (Leubnitz). 162 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 48 records from SYMBIOSE_2017_12_18. 163 records from Type Localities of Heteroptera (Insecta: Hemiptera) from Turkey. 39 records from Suivi des reptiles en forêt du Madrillet. 7 records from Données naturalistes de Nicolas LEGRAND. 43 records from SA Flora (BDBSA). 20 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 23 records from The genus Rosalba Thomson, 1864 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 1005 records from Computarización de la Colección Paleontológica de la Secretaria de Medio Ambiente, Vivienda e Historia Natural, del estado de Chiapas. 11 records from Revision of the Oriental Genus Physodera Eschscholtz, 1829 (Coleoptera, Carabidae, Lebiini, Physoderina), with the descriptions of two new species. 5 records from A new species of Microdeutopus, M. periergos sp. nov. (Crustacea, Amphipoda, Senticaudata, Aoridae) from Cyprus (East Mediterranean Sea). 6303 records from Atlas de coleópteros Scarabaeoidea de México. 38 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific. 1 records from Aphis species (Hemiptera, Aphididae) living on Mulinum (Apiaceae) in South America, with a description of a new species. 753 records from Small Mammal Trapping 08. 82 records from DREAL_PACA_-_N2000_-_Ville_de_Fréjus_2017_12_18. 29 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 28 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 658 records from Annotated zoogeography of non-marine Tardigrada. Part IV: Africa. 247 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 66 records from Biosphärenreservat Münsinger Alb. 3 records from Range table from planktonic foraminifers in ODP Hole 182-1130A. 16 records from Foraminifera abundance of Hole 60-454. 156 records from (Table 9) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-587. 160 records from Schulbiotop Dr.-Gustav-Schickedanz-Hauptschule (Fürth). 158 records from Frauenholz (Holzmaden). 2742 records from UCM Fish Collection (Arctos). 80 records from Two new Hyphessobrycon (Characiformes: Characidae) species from Central Amazon basin, Brazil. 2 records from Gluphisia irene, a new species (Lepidoptera, Notodontidae) from China and some taxonomical remarks about the palaearctic Gluphisia Boisduval, 1828. 1158 records from Dipterists Forum: Field Week 2002 (Inverness). 105 records from Gwaii Haanas Marine Plants (OBIS Canada). 9 records from (Table 6) Distribution of late Eocene calcareous nannofossils in ODP Hole 149-899B. 65 records from Mammalians Specimens of Akita Prefectural Museum. 3302 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 168 records from Fig. 3. Pollen record of profile PG1228 from lake Levinson-Lessing. 28 records from (Figure 8) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-632A. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 112 records from (Table 13) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-667A. 582 records from Gorgonacea specimens of Kuroshio Biological Research Foundation. 756 records from Especies de Anopheles en el sur de México y su distribución geográfica actual con enfoque en taxonomía clásica y molecular. 6 records from Nannofossil abundance of Hole 17-165. 60 records from UWIZM Echinoderms. 203 records from Schanzenanlage Bergham. 93 records from Schulgelände des Schulzentrums am Himmelsbarg. 146 records from Supplement to the Checklist of water mites (Acari: Hydrachnidia) from the Balkan peninsula. 50 records from Concentration of siliceous microplankton in surface sediments, size fraction 20-40 µm. 281 records from Diplopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 192 records from BIRDRACE Emslandracer. 365 records from Freshwater Shad Monitoring Data. 28 records from UWIZM Birds. 144 records from Monitoreo biológico en la cuenca Jamundí - Subcuenca Pance Campaña ARA - RARE - CVC – Asociación Calidris. 151654 records from BioFokus. 1432 records from Reptilia notes, NTNU University Museum. 6 records from Données naturalistes de Sandrine CHEYPPE-BUCHMANN. 1 records from A new species of Limnephilidae (Insecta: Trichoptera) from the Western Alps (Insecta: Trichoptera). 615 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 18948 records from SEWBReC Dragonflies and Damselflies (South East Wales). 56 records from Tejidos colectados en la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 62 records from Spotted crake national survey in the UK in 1999. 144 records from Cactophilic Drosophila and Opuntia. 105876 records from Countryside Council for Wales - Welsh Peatland Invertebrate Survey (WPIS). 55 records from Diversity of marine bryozoans inhabiting demosponges in northeastern Brazil. 304 records from Données naturalistes d'Eléonore VANDEL. 10963 records from Flora von Deutschland (Phanerogamen). 2 records from Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil. 246689 records from Mollusc (non-marine) data for Great Britain and Ireland. 4 records from Review of the fish genus Epinnula Poey (Perciformes: Gempylidae), with description of a new species from the Pacific Ocean. 4033 records from Plants, herbivores and their natural enemies along a grassland management gradient 2008. 1 records from A new species of Otothyropsis (Siluriformes: Loricariidae) from the upper Río Paraná basin, Paraguay, with a discussion of the limits between Otothyropsis and Hisonotus. 3456 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 1 records from A new species of smooth-skinned Spinomantis frog (Anura: Mantellidae) from south-eastern Madagascar. 1 records from A new species of the genus Microhyla (Anura: Microhylidae) from Eastern Nepal. 1627 records from House Sparrow Parks Project, London, 2009-2010. 28 records from A new Neotibicen cicada subspecies (Hemiptera: Cicadidae) from the southeastern USA forms hybrid zones with a widespread relative despite a divergent male calling song. 65 records from Abundance of benthos infauna at station POS128/2_267. 15 records from Range table from planktonic foraminifers in ODP Hole 171-1051A. 19 records from Planktic foraminifera abundance of Hole 60-458. 7 records from (Table 8B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 5-2 through 8-4. 10211 records from USBombus, contemporary survey data of North American bumble bees (Hymenoptera, Apidae, Bombus) distributed in the United States. 2731 records from Diversité des Poissons de Nouvelle-Calédonie, pêche à la ligne à main. 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 6 records from Two new giant pill-millipede species of the genus Zoosphaerium endemic to the Bemanevika area in northern Madagascar (Diplopoda, Sphaerotheriida, Arthrosphaeridae). 5 records from A morphological and molecular study of Psilops, a replacement name for the Brazilian microteiid lizard genus Psilophthalmus Rodrigues 1991 (Squamata, Gymnophthalmidae), with the description of two new species. 1 records from Description of a new species of Cnemaspis (Squamata: Gekkonidae) from Knuckles Range of Sri Lanka. 156 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE6. 200 records from Occurrence of mammalia relicts at site Zawalona Cave. 88 records from Great Crested Newt Special Area of Conservation (SAC) Monitoring Data. 30 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 1721 records from Insects specimen database of Osaka Museum of Natural History. 84 records from E.C. Manning Park Collection. 7119 records from Electronic Atlas of Ichthyoplankton on the Scotian Shelf of North America (OBIS Canada). 45935 records from UF Florida Museum of Natural History Mammals. 2 records from A new species of seahorse (Teleostei: Syngnathidae) from the South China Sea. 350 records from (Table 6) Distribution of planktonic foraminifera in the late Oligocene to middle Miocene section of ODP Hole 149-898A. 4 records from Two new species of the genus Podalonia Fernald from China and a key to the Chinese species of the genus (Hymenoptera: Sphecidae). 6 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14. 4127 records from University of Bergen, Gastropoda. 122 records from Biosphärenreservat Mittelelbe. 39 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 117-728A. 32 records from Benthic macrofauna abundance of sediment core 13077-070. 378 records from (Appendix A) Radiolarian abundances in sediment core MD96-2086. 124 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 90 records from Nannofossil abundance of Hole 49-407. 7 records from Nannofossil abundance of Hole 8-75. 18 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 388 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 1257 records from Waarneming.nl (NL) - Great Grey Shrike Count 2010-2011. 22 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 16 records from Distribution of meiobenthos in sediment core M19_232-2 of the northeastern Atlantic (Table 1). 69 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 6 records from Range table from planktonic foraminifers in ODP Hole 146-891B. 17 records from Planktic foraminifera abundance of Hole 11-98. 114 records from Occurrence of mammalia relicts at site Nikolaushöhle. 12 records from The goblin spider genus Ischnothyreus (Araneae, Oonopidae) in Java and Sumatra. 147 records from Occurrence of mammalia relicts at site Felsställe. 99 records from Occurrence of mammalia relicts at site Erd. 45 records from Occurrence of mammalia relicts at site le gisemnet de Fongabon. 3124 records from ConDidact Citizen Science Surveys - Snails 2015. 208 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 344 records from 20 Jahre Naturschutzgebiet Dreienberg. 85702 records from TTU Mammals Collection. 40 records from Pollen profile from sediment core Fiekers Busch. 387 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE278. 1346 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 22 records from (Table 2) Documentation of vital effect change in Coccolitophorides above the FAD Emiliania huxleyi in DSDP Site 90-594 east of South Island, Southwest Pacific. 8 records from Revision of the stag beetle genus Ryssonotus MacLeay (Coleoptera: Lucanidae), with descriptions of a new genus and three new species. 10 records from Nannofossil abundance of Hole 94-610C. 10 records from Nannofossil abundance of Hole 31-297. 9 records from Nannofossil abundance of Hole 6-47. 96 records from Lower Albian Mazagan Plateau (Oceanic Anoxic station 1b) range chart, DSDP Site 545. 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 66 records from Diatom assamblage in samples from sediment trap OG4. 272 records from Loup 2013 présence régulière communale (réseau Loup-Lynx ONCFS). 38 records from Naturalis Biodiversity Center (NL) - Paleobotany. 22 records from Waldwiese. 204 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 2 records from Second record of Lasiurus ebenus (Chiroptera, Vespertilionidae), with comments on its taxonomic status. 33 records from Biotop "Kohlbeke" (Berlin-Marzahn). 36 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 19 records from A revision of the trapdoor spider genus Liphistius (Mesothelae: Liphistiidae) in peninsular Malaysia; part 1. 390 records from Crustacea ZMK. 1 records from New records of eriophyoid mites from Iran (Acari: Trombidiformes: Eriophyoidea) and a description of a new Brevulacus Manson species. 395 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 2 records from A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 4 records from Bellendenker gen. nov., a new Australian genus of Glandulariini (Coleoptera: Staphylinidae: Scydmaeninae). 3 records from First two species of Austroleptis Hardy (Diptera: Brachycera: Austroleptidae) from Brazil. 3 records from A new species of Arctoseius Thor, 1930 (Acari: Ascidae) from taiga regions of the Palaearctic, with a key to Arctoseius species of Fennoscandia, NW Europe. 1157 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 32 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 4316 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 46 records from Macroalgae of the Balleny Islands and western Ross Sea, Southern Ocean. 7 records from Review of the genus Pityocona Meyrick, 1918 (Lepidoptera: Gelechiidae) in China, with descriptions of five new species. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 270 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 8 records from ZFMK Siphonaptera collection. 1 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0011B. 2488 records from ISU Birds. 12 records from Pristimantis antisuyu sp. n. and Pristimantis erythroinguinis sp. n., two new species of terrestrial-breeding frogs (Anura, Strabomantidae) from the eastern slopes of the Andes in Manu National Park, Peru. 690 records from Fishes of the flooded savannas of Paz de Ariporo, Meta River, Orinoco basin. 4 records from The species group Amabilis of the genus Euplocania Enderlein (Psocodea: Psocomorpha: Ptiloneuridae). 58626 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Trawl. 4 records from Two new species of Halictophagidae (Insecta: Strepsiptera) including the first record of genus Coriophagus Kinzelbach from India. 4 records from Taxonomic revision of Paraustrosimulium Wygodzinsky & Coscarón: reassignment of Austrosimulium colboi and description of P. obcidens n. sp. from Western Australia. 2491 records from Actualización de la base de datos computarizada de la colección ictiológica de la Universidad Autónoma de Baja California. 111 records from EPAMA "Vallée de la Meuse"/2006 (Etude ESOPE). 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 4 records from Taxonomic revision of the Protopolybia sedula species-group (Hymenoptera, Vespidae, Polistinae), with an new identification key to species. 21 records from Unveiling a surprising diversity of the genus Diopatra Audouin & Milne Edwards, 1833 (Annelida: Onuphidae) in the Macaronesian region (eastern North Atlantic) with the description of four new species. 2 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 11 records from A new species catfish, Amphilius pagei (Siluriformes: Amphiliidae) from Angola. 18 records from New species of Andiorrhinus Cognetti, 1908 (Oligochaeta: Rhinodrilidae) from Venezuela and Brazil. 1 records from A review of the genus Triancyra Baltazar (Ichneumonidae: Rhyssinae) from Vietnam, with descriptions of three new species. 28 records from (Table 1) Benthic foraminifer stratigraphy of ODP Site 166-1006 sediments. 216 records from Planktic foraminifera abundance of Hole 49-407. 6 records from Planktic foraminifera abundance of Hole 84-568. 2 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 64 records from Maschwiesen Laatzen. 66 records from Pottundkopp. 4 records from Analyses of the recent components of sediment core PS1014-1. 22226 records from SER Site-based Surveys. 78 records from Marine Invertebrate Diversity Initiative (OBIS Canada). 220 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 2544 records from Nekton and plankton counts from RMT (320 µm) hauls of cruise GAE 1975/76. 1854 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 8 records from (Table 1) Relative abundances of Maastrichtian benthic foraminifera at El Kef, Part I. 46 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-9. 32 records from Benthic macrofauna abundance of sediment core 13077-093. 1430 records from (Appendix 2) DSDP Site 94-610 ostracode species census data. 30 records from Nannofossil abundance of Hole 24-236. 3 records from Nannofossil abundance of Hole 2-11. 181 records from Nannofossil abundance of Hole 64-474. 74 records from Feuchtwiese in Langes Tannen (LMS), Klasse 5c. 65 records from Rur. 12 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 30 records from Kohlbach (Sulzfeld). 62 records from Schulgelände Lise Meitner Realschule (Paderborn). 136 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 24 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 8217 records from Insect specimens of Kashihara City Museum of Insect. 10656 records from Crispin S. Guppy Collection. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 15575 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 4 records from First record of Hiroshiinoueana Kawabe, 1978 from China (Lepidoptera: Tortricidae: Olethreutinae), with descriptions of two new species. 4 records from Four new earthworm species of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae). 10 records from Populations ensauvagées de Lapin de garenne en Nouvelle-Calédonie issues du CEN-NC. 2013. 196 records from Nannofossil abundance of Hole 18-173. 51 records from Nannofossil abundance of Hole 67-499B. 15 records from Nannofossil abundance of Hole 67-494A. 87 records from Nannofossil abundance of Hole 59-448. 2 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 8 records from Nannofossil abundance of Hole 7-65. 348 records from Nannofossil abundance of Hole 78-541. 5 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 3 records from Two new species of Jungiella (Diptera: Psychodidae: Psychodinae) from the Palaearctic Region. 40 records from Microzooplankton abundance and biomass at station TT045_2-1. 126 records from Liether Kalkgrube. 156 records from Wulfsmuehle/Pinnau. 82 records from Mainufer. 72 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 1052 records from Biodiversidad de coleópteros y arañas de las Sierras de Taxco-Huautla. 2 records from Two new species of the Rhopalopsole magnicerca group (Plecoptera: Leuctridae) from China. 9 records from The Neotropical sharpshooter genus Ruppeliana Young (Insecta: Hemiptera: Cicadellidae): four new species, key to males, and new synonyms. 1 records from Two new species and new records of the genus Parachironomus Lenz, 1921 (Diptera, Chironomidae) from northern Russia. 180 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 4595 records from Weddell Seal census, Vestfold Hills, Antarctica. 1790 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 354 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 7210 records from Atlas of the Amphibians and Reptiles of Poland. 73 records from Lichen herbarium, UiB. 37 records from Studies on Gripopterygidae (Plecoptera) from Espírito Santo State, Brazil. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 196 records from Biodiversity and notes on carabid beetles from Angola with description of new taxa (Coleoptera: Carabidae). 1549 records from Actualización de la Colección de Collembola de México y ácaros edáficos. Catálogo de oribátidos de México. 6682 records from Observaciones de Especies Silvestres (by Charif Tala). 35200 records from Herpetology Collection - Royal Ontario Museum. 2206 records from Amphibians and reptiles of Ireland. 3 records from Three new endemic Aphyosemion species (Cyprinodontiformes: Nothobranchiidae) from the Massif du Chaillu in the upper Louessé River system, Republic of the Congo. 16504 records from CUMV Amphibian and Reptile Collection. 4064 records from Native Species Surveys Across Wales (1978 to 2006). 302 records from Mamíferos del piedemonte de la sabana de la Orinoquia. 830 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Orthoptera (ZUFMS-ORT). 33 records from Occurrence of mammalia relicts at site Rotselaar. 1 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 46 records from Schulgelände IGS Kaufungen. 236 records from Rotifers of Macquarie Island. 40 records from Coarse fraction analysis of sediment core PS1730-2. 54239 records from SDNHM Birds Collection. 14 records from Phytoplankton abundance during Akademik Vernadsky cruise AV22. 844 records from Antarctic Krill Euphausia superba. 2347 records from Shellfish (GNHM-MS). 96 records from Macrofauna biomass in surface sediment sampled during cruise DI229. 65 records from Meiofauna abundance in sediment core 12930-007. 13 records from Nannofossil abundance of Hole 7-62. 7 records from Nannofossil abundance of Hole 3-16. 2303 records from Lepidoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 176 records from BIRDRACE Vogelkucker. 36 records from Artenvielfalt auf der Wiese. 2 records from New species and new synonymy in Neoibidionini (Coleoptera, Cerambycidae). 241 records from Revision and phylogenetic analysis of the orb-weaving spider genus Glenognatha Simon, 1887 (Araneae, Tetragnathidae). 8190 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Pisces (ZUFMS-PIS). 7 records from L'Entomologiste [1944- ]. 221 records from City of Edinburgh Natural Heritage Service - General Public Records.. 545304 records from Florida Keys Reef Visual Census 2007. 906 records from SIO_FAMIZ. 22964 records from Norfolk and Suffolk Broads Invertebrate Data 2007-2008. 518 records from Review of Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae) from Espíri- to Santo, Brazil, with description of twenty-one new species. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 55948 records from CSIRO Ichthyology provider for OZCAM. 16 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 68 records from Freshwater Gastropods of Taveuni. 2 records from A new species of Lobesia Guenée, 1845 from Thailand (Lepidoptera: Tortricidae: Oletheutinae). 2 records from Rhinobatos manai sp. nov., a new species of guitarfish (Rhinopristiformes: Rhinobatidae) from New Ireland, Papua New Guinea. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 6 records from New species of Chimerothalassius Shamshev & Grootaert (Diptera: Dolichopodidae: Parathalassiinae) from the West Indies and Costa Rica. 1 records from Pseudoleptonema tansoongnerni new species (Hydropsychidae: Trichoptera) with species list of Trichoptera from Li Phi Falls, Mekong River, southern Laos. 5 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 1942 records from BioGIS - Marine snails - HUJ collections. 4804 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 10102 records from Zooplankton Abundancies White Sea, 1972. 14 records from Données naturalistes de Pierre ZAGATTI. 235 records from Estado de salud y estatus de conservación de la(s) población(es) de totoaba (Totoaba macdonaldi) en el Golfo de California: una especie en peligro de extinción. 1 records from Description of a new Oriental stonefly species, Phanoperla constanspina (Plecoptera: Perlidae) from Mindanao, Philippines and association of life stages using DNA barcoding. 33737 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Gill Net. 24271 records from MBML-Peixes - Coleção de Peixes. 10 records from Phortica eparmata species complex (Diptera, Drosophilidae) from the Oriental Region, with DNA barcoding information of Chinese species. 1 records from A new species of Dohrnemesa and a new species of Polauchenia from Brazil (Hemiptera: Heteroptera: Reduviidae: Emesinae). 2 records from Order Hymenoptera, family Bethylidae Genus Glenosema Kieffer. 3450 records from Fishes in MZNA-VERT: ecological assessment of the Aragon river in Sangüesa (Spain). 1486 records from Early succession in benthic hard bottom communities in Kongsfjorden, Svalbard - abundance. 5 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 12 records from Pollen and spore abundance of Hole 42-381. 1 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 5 records from Range table from planktonic foraminifers in ODP Hole 167-1018A. 4 records from Range table from planktonic foraminifers in ODP Hole 167-1014A. 18 records from Planktic foraminifera abundance of Hole 28-264A. 16 records from Occurrence of mammalia relicts at site Henauhof NW 2. 594 records from (Appendix B5) Distribution of planktic foraminifera in DSDP Site 90-594 east of New Zealand. 160 records from Duck sightings per month, Macquarie Island. 14602 records from CNPE/Coleccion Nacional de Peces. 230 records from Nivå Bay species list, Zealand, Denmark. 9170 records from LSUMZ Herps Collection. 10 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 142 records from Schussenaue bei Berg. 3464 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 14522 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 13 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 12 records from Catalogue of the Teratomyzidae (Diptera, Opomyzoidea) of the World. 2 records from A new species of Phrynobatrachus (Anura: Phrynobatrachidae) from the Eastern Arc Mountians of Tanzania. 7 records from Stenochironomus munteanpurin sp. n., a new leaf-mining species from Brazil (Diptera: Chironomidae). 5 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 917519 records from SEWBReC Birds (South East Wales). 4 records from The family Passandridae (Coleoptera: Cucujoidea) in Argentina with comments on species from Brazil and Paraguay. 4 records from A new species of Puddle Frog, genus Phrynobatrachus (Amphibia: Anura: Phrynobatrachidae) from Ghana. 2 records from Review of the genus Agonochaetia Povolný (Lepidoptera, Gelechiidae), and description of a new genus and species from the Canary Islands. 850 records from Crossbills, Distribution survey in Great Britain, 1995-2005. 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 4066 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 2 records from Two new species of cave-dwelling Charinus Simon, 1892 from Brazil (Arachnida: Amblypygi: Charinidae). 12 records from Two new species of the genus Criotettix Bolivar, 1887 (Orthoptera: Tetrigidae: Scelimeninae) from India. 1 records from Taiwanese species of the ant genus Technomyrmex (Formicidae: Dolichoderinae). 1 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 1385 records from Countryside Council for Wales - Amphibian & Reptile Licence Return Data. 1662 records from Inventarios de flora y fauna en el piedemonte de los municipios Aguazul, Tauramena y Yopal del departamento de Casanare. 13 records from Two new species of Adapterops (Coleoptera: Anthribidae) from protected areas of northern Madagascar, with a key to species, and new faunistic data on the genus. 1984 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 266400 records from Freshwater samples in MZNA-INV-FRW: Macroinvertebrate samples from the water quality monitoring network along the Ebro Basin. 1 records from Acanthopagrus taiwanensis, a new sparid fish (Perciformes), with comparisons to Acanthopagrus berda (Forsskål, 1775) and other nominal species of Acanthopagrus.. 724 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 8484 records from Lizard Island Research Station. 2 records from New species and records of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Africa and Asia. 526876 records from Caddisfly (Trichoptera) records from Britain and Ireland to 2012. 20 records from Analyses of the recent components of sediment core PS1402-2. 103 records from WNMU Mammal Collection (Arctos). 1 records from Drepanosticta emtrai sp. nov. from Vietnam with a discussion of Drepanosticta vietnamica Asahina, 1997 (Odonata: Zygoptera: Platystictidae). 1300 records from (Table 2) Distribution and abundance of selected planktonic foraminifera of the Pliocene DSDP Hole 41-369A. 762 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 1384 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE218. 2 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 805 records from (Table T2) Biogenic and mineral composition of sediments cored in Vaale, Schleswig-Holstein. 32 records from Benthic macrofauna abundance of sediment core 13200-008. 30 records from Nannofossil abundance of Hole 11-104. 249 records from Chironomid remains in the sediment sequence of Site PG1212. 16 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 40 records from Microzooplankton abundance and biomass at station TT045_11-2. 508 records from Données Rhopalocères et Zygènes du CEN Aquitaine, programme 64PRED. 114 records from Revision of the ant genus Mayriella.. 39 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 96 records from Streuobstwiese Stedar. 164 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 144 records from Birdrace-Buteo2DO-Dortmund. 504 records from Ants on Nukunonu atoll in 2011. 34 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 1382 records from Distribution of Hares in Greater Manchester. 6 records from A review of the genus Baiocis Browne, 1962 (Coleoptera: Curculionidae: Platypodinae), with new species, new synonymy and a key to males. 2 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 65 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 6867 records from Base de datos de mamíferos de México depositados en colecciones de Estados Unidos y Canadá. 118 records from Succession of benthic hard-bottom communities abundance at X-Huinay, Comau Fjord, Chile, in 2012. 5 records from Données naturalistes de RENAUD Maëla. 990 records from Mamíferos: Colección Universidad de Caldas. 417058 records from Mayfly (Ephemeroptera) Data for Great Britain for 1906-2017. 124 records from Données naturalistes de Guillaume MARCHAIS. 16734 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 101 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Nematoda (ZUFMS-NEM). 8 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 17244 records from Coleccion de Ictiología del Instituto de Ciencias Naturales (ICN-MHN-Ic). 15 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 6 records from Colección de referencia del Laboratorio de Zooarqueología del INAPL (INAPL/LZ). 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 3 records from Vietelmis jablonskii, a new species of riffle beetle from Laos and Thailand and new faunistic records on Vietelmis Delève, 1968 from Malaysia (Coleoptera: Elmidae). 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 30361 records from World distribution of the aquatic Oligochaeta. 44 records from Ictiofauna Asociada a los Cativales del Municipio de Riosucio, como Aspecto Relevante dentro de la Estructura Ecológica Principal del Chocó Biogeográfico. 578 records from Hokkaido University Coleoptera Collection. 16 records from Description of a new group of species of Edessa (Hemiptera: Pentatomidae: Edessinae). 2 records from First record of the genus Soliperla (Plecoptera: Peltoperlidae) from China with description of a new species. 1 records from Revision of the genus Metaterpna Yazaki, 1992 (Lepidoptera, Geometridae, Geometrinae), with description of a new species from China. 299 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 5 records from Description of a new species of Chimarrhometra Bianchi, 1896 (Hemiptera: Heteroptera: Gerridae) from China. 8 records from Two new species and a new record of Metacirolana Kussakin, 1979 (Crustacea: Isopoda: Cirolanidae) from Indonesia. 3470 records from Amphibian observations from Nida Valley. 6 records from Range table from planktonic foraminifers in ODP Hole 146-889A. 6 records from Planktic foraminifera abundance of Hole 14-140. 77 records from Occurrence of mammalia relicts at site Oblazowa 2. 15 records from The tip of the iceberg: a distinctive new spotted-wing Megaselia species (Diptera: Phoridae) from a tropical cloud forest survey and a new, streamlined method for Megaselia descriptions. 2 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200800. 19 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 90 records from Innenstadt Göttingen - Natur Zuhause. 66 records from Flux data of NU2_trap (Table A1). 5757 records from Database on Forest Disturbances in Europe. 114 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 4 records from (Supplement Table 5) Percentage cover abundance of plants recorded at the Primary Site on Disko Island. 5043 records from Distribución geográfica de las aves y los mamíferos del estado de Querétaro. 102 records from Occurrence data of new Afrotropical and Oriental Mydidae (Diptera: Asiloidea). 27 records from Pollen data of trap CB4. 330 records from (Table 3a and b) Median biomass of macrobenthos in surface sediments. 7632 records from Antarctic Jellyfish. 48 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 33 records from Meiofauna abundance in sediment core 13077-058. 242 records from Loup 2013 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 54 records from Nannofossil abundance of Hole 94-610. 88 records from Nannofossil abundance of Hole 67-500. 5 records from Nannofossil abundance of Hole 6-53A. 9 records from Phytoplankton abundance at station DI182_11860#6. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 40 records from Microzooplankton abundance and biomass at station TT045_9-2. 48450 records from Corncrake national surveys - raw data. 761 records from Inventaire du Lac de Marcenay (Bourgogne). 7 records from Revision of the genus Coeligetes from Malaysia and Indonesia, and description of Coeligetoides gen. nov. (Coleoptera: Chrysomelidae: Galerucinae). 246 records from Rohrmeistereiplateau und angrenzendes Gebiet. 46 records from Wiese Niederaula. 90 records from Ehmkendorf. 9514 records from 2010-2013 Beetle Data from Machair LIFE+ Project Plots. 6 records from Dicharax (?) candrakirana n. sp. (Gastropoda: Cyclophoridae) from Sempu Island, Indonesia. 16 records from Descriptions of four new sponge-inhabiting barnacles (Thoracica: Archaeobalanidae: Acastinae). 7 records from Discovery of the genus Claraeola Aczél in Iran with the description of two new species (Diptera: Pipunculidae). 1 records from Dinoxyleborus Smith, a new genus of Neotropical xyleborine ambrosia beetle (Coleoptera, Curculionidae: Scolytinae). 32 records from Microzooplankton abundance and biomass at station TT043_6-1. 76 records from Faunal assemblage of sediment core GS7603-12. 2 records from 5. Wiener Gemeindebezirk. 86 records from Schulgarten-St.-Georg-Gymnasium. 339 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 68 records from Erft in Selikum (Neuss). 36 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Mollusca (ZUFMS-MOL). 23 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 222 records from Interacciones en el dosel de la selva húmeda tropical e implementación de un sistema de estudio en este ambiente. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 1 records from Synthèse de la Répartition des populations d'isard en 1994 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2900 records from Bases para el monitoreo de dos especies de carnívoros medianos en la Reserva de la Biosfera de Mapimí, Durango. 2 records from A new species of Brasineura Silva-Neto & García Aldrete (Psocodea, ‘ Psocoptera’, Ptiloneuridae), with comments on morphological variation in B. troglophilica and a revised generic diagnosis. 40 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 3497 records from Insect specimens of Otaru City Museum. 98 records from City of Edinburgh Natural Heritage Service - Green Hairstreak Survey. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 7 records from Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species. 12 records from New species and records of pollen and sap beetles for Iran (Coleoptera: Kateretidae, Nitidulidae). 58 records from Coeroeni/Sipaliwini River Expeditions 1988/1989. 2289 records from Specimen records of spiders (Arachnida: Araneae) by monthly census for 3 years in forest areas of Yakushima Island, Japan. 106400 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 5 records from Some taxonomic notes on the Caradrina (Eremodrina) filipjevi (Boursin, 1936) species group (Lepidoptera, Noctuidae). 39 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1171A sediments. 323 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 11 records from Subantarctic Fur sealsat Heard Island, 1987/88. 1 records from The importance of correct labelling of types: an example in Tortricidae (Lepidoptera) and its rectification. 24954 records from Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by English Nature. 30 records from Undercover speciation of wentletraps (Caenogastropoda: Epitoniidae) in the Southwestern Atlantic. 111 records from Caracterización ecológica de reptiles presentes en los bosques subxerofíticos de Unguía, Chocó. 64 records from Taxonomic notes on a collection of jumping spiders from Iran (Araneae, Salticidae). 12652 records from Other Mammal Data from National Dormouse Monitoring Programme (NDMP). 18 records from DREAL_PACA_-_N2000_-_Latitude_2017_12_18. 1 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 72903 records from Atlas des rhopalocères du Nord et du Pas-de-Calais. 2 records from The ants of El Hierro (Canary Islands).. 810 records from SNH Great crested newt records. 5 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 1 records from Periclimenoides tyrannodentatus, a new species of symbiotic shrimps (Crustacea: Decapoda: Palaemonidae) from Taiwan. 226 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE7. 495 records from Occurrence of the most important taxa of macrofauna on Voering Plateau, Tab.10b,11b,14b. 8 records from Two new rapacious nematodes from intertidal sediments, Gammanema magnum sp. nov. and Synonchium caudatubatum sp. nov. (Nematoda, Selachinematidae). 360 records from Planktic foraminifera abundance of Hole 47-397. 4 records from Planktic foraminifera abundance of Hole 63-468B. 396 records from (Table 3) Distribution and abundance of selected planktonic foraminifera of the Pliocene DSDP Hole 41-366A. 5 records from Planktic foraminifera abundance of Hole 84-569. 9 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 314 records from Ictiofauna balseana y helmintos parásitos asociados. 111 records from Occurrence of mammalia relicts at site Villa Seckendorff. 6308 records from Hormigas en cafetales con diferente intensidad de manejo en el departamento del Cauca. 472 records from McMaster University Collection. 48 records from (Table 3) Pliocene/Pleistocene ostracodes from ODP Hole 104-642C. 1040 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 315 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 10 records from Nannofossil abundance of Hole 94-609C. 2383 records from Données naturalistes d'Annegret NICOLAI. 82 records from Microfossil abundance of Hole 18-173. 106 records from Sylter Meerstrandläufer. 15 records from Schulgarten Zinnowwald-Grundschule. 90 records from Microzooplankton abundance measured on water bottle samples at station PS58/045-2. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_29-6. 81 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 965 records from UWIZM Fish Collections. 248 records from BIRDRACE Immerwiederhopf. 58 records from Insekten. 60 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 236 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 18889 records from Bob Merritt dataset of Nottinghamshire invertebrates. 44592 records from Mammals housed at MHNG, Geneva. 66 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 20891 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 6034 records from Reiner Richter Odonata. 1 records from Revision of the genus Adelogorgia Bayer, 1958 (Cnidaria: Anthozoa: Octocorallia) with the description of three new species. 2 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 14 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 4 records from Données naturalistes de Charlie PICHON. 3 records from Lost species in Cameroon: rediscovery of the endangered freshwater crab, Louisea balssi (Bott, 1959) (Brachyura: Potamonautidae), with notes on its ecology and conservation. 1 records from Notes on Oriental and East Palaearctic Manota Williston (Diptera, Mycetophilidae), with the description of seven new species. 319 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 2 records from A new genus and new species of Meropathina from Lord Howe Island (Coleoptera: Hydraenidae). 5761 records from Données naturalistes de Pascal PEYRACHE. 2 records from Confirmation of the identity of the type host of the louse Halipeurus fallacis (Phthiraptera: Philopteridae). 57304 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 26 records from Systematics of Thiodinini (Araneae: Salticidae: Salticinae), with description of a new genus and twelve new species. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 7612 records from USGS SESC - Everglades - Herpetofauna - 2005. 4 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LI
Keywords: GBIF; biodiversity; species occurrences